Heat-conductive structure, and molding, coated film, sheet and adhesive layer being the heat-conductive structure
Patent Information
- Application Number
- JP2023149433
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-14
- Publication Date
- 2025-03-27
Smart Images

Figure 2025042423000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive structure in which a base material contains "a group of carbon nanofibers containing carbon nanofibers having a specific shape," and to a molded body, coating film, sheet, or adhesive layer that is the thermally conductive structure. [Background technology]
[0002] In recent years, there has been a demand for improved performance in various aspects of electronic components installed in automobiles, airplanes, computers, various measuring devices, etc., and the materials used therein. In particular, materials used to dissipate heat from electronic components and devices are required to have higher performance, and the required characteristics are increasing year by year. In particular, materials with higher thermal conductivity and non-conductivity are required.
[0003] Specifically, because of their small particle size, they can be used in narrow spaces such as electronic components, and by utilizing their high thermal conductivity (independent of direction) and anisotropy, it is possible to pursue even higher performance, and structures and materials that can be made lighter than those using other thermal conductive materials are desired.
[0004] However, there are few substances with a particle size of less than 5 μm (high aspect ratio) and high thermal conductivity. One well-known substance is carbon nanotubes (CNTs), but they are difficult to disperse and orient, and have not yet been put to practical use. Various types of whiskers (metal, inorganic single crystal) are also possible, but they are difficult to manufacture and very expensive, so they have not yet been put to practical use.
[0005] On the other hand, fibrous carbon and carbon fiber reinforced plastics (CFRP) are lightweight, have high thermal conductivity, and are also strong, so they are widely used as substitutes for metals in various structures and molded products.
[0006] The shortest fibrous carbon is also called carbon milled fiber, and generally has an average fiber length of 70 μm to 200 μm and an average fiber diameter of about 3 μm to 10 μm (3,000 nm to 10,000 nm). Because of its small shape (size), it is often used as an abrasive, reinforcing agent, auxiliary agent, etc.
[0007] Chopped fiber and long fiber, which have a longer average fiber length than carbon milled fiber, are primarily used in molded products such as prepregs and forged products. In addition, fine CFRP made by further crushing carbon milled fibers to shorten the fiber length is used, for example, as a concrete reinforcing material. However, the shorter the particle diameter, the more difficult it becomes to process the particles, and the particles are more likely to aggregate after being pulverized. Therefore, at present, the particles are of little value in fields where good dispersion is required.
[0008] If we define fibrous carbon simply based on its shape (size), without considering the actual dispersion of the fibrous carbon (the presence of each individual fiber) or the utility and usability of the fibrous carbon, the currently known general definitions are "carbon milled fiber defined as having a diameter of 3 μm to 10 μm and a length of 30 μm to 10,000 μm," "carbon nanofibers with a diameter of 50 nm to 1,000 nm and a length of 0.2 μm to 200 μm," and "carbon nanotubes with a diameter of 0.4 nm to 100 nm and a length of 50 nm to 20,000 nm."
[0009] Although there are documents that describe the diameter and aspect ratio of fibrous carbon (for example, Patent Documents 1 and 2), currently there are almost no fibrous carbon groups of carbon nanofibers that have a small shape (size) like that of the present invention, a particularly large aspect ratio, and are in a state where they can be isolated (separated) approximately one by one, or are in a state where they can be dispersed (dispersed) approximately one by one. At present, there are almost no carbon nanofibers having a good shape (size) as defined above, and the utilization rate of fibrous carbon having the carbon nanofiber size is extremely low due to its poor dispersibility or redispersibility, etc.
[0010] In addition, there is no commercially available carbon fiber on the market that has nano-sized carbon fibers with a large aspect ratio dispersed therein or that is in a dispersible state. This is thought to be because the carbon fibers used as the raw material are specifically and neatly split vertically when they are crushed, in other words, the raw filaments cannot be peeled off from the filaments in an appropriate manner. Therefore, there is no known dispersion in which "fibrous carbon such as carbon nanofibers" having a large aspect ratio as in the present invention is stably dispersed.
[0011] Carbon nanofibers have a large aspect ratio and are dispersible and stable in dispersion, and are expected to have a wide variety of demands (applications). However, until now, they have not been successfully produced, and it has not been possible to produce nanofibers with good dispersibility or dispersion stability.
[0012] On the other hand, for example, Patent Documents 3 to 5 disclose techniques that attempt to increase the thermal conductivity of a structure obtained by simply incorporating fibrous carbon in a resin, without taking into account the size and dispersibility of the fibrous carbon.
[0013] Patent Document 3 describes a thermally conductive sheet containing a curable resin composition, fibrous carbon, and a filler that aligns the fibrous carbon in a predetermined direction, in which the fibrous carbon is oriented along the thickness direction of the thermally conductive sheet, and the filler contains at least aluminum nitride. It is also described that the average fiber length of the fibrous carbon is preferably 100 μm or more.
[0014] However, the fibrous carbon used in Patent Document 3 has a length of 100 μm or more, and does not have the above-mentioned "carbon nanofiber (CNF) defined by size," so it cannot be used in narrow areas of electronic components, etc., and in addition, the anisotropy of the thermal conductivity is too large and the thermal conductivity in the non-oriented direction is extremely low, resulting in a low total thermal conductivity and insufficient heat dissipation.
[0015] Patent Document 4 describes a thermally conductive sheet containing 55 to 70% by volume of fibrous carbon, a thermally conductive filler containing at least one of aluminum nitride, aluminum oxide, and aluminum hydroxide as an inorganic filler, and 30 to 45% by volume of a two-liquid addition reaction type silicone.
[0016] However, the fibrous carbon used in Patent Document 4 is not limited in size, and there is no "carbon nanofiber (CNF) defined by size" as described above. In the examples of Patent Document 4, the average fiber length is 100 μm and the average fiber diameter is 9 μm, which means that the fiber cannot be used in narrow areas such as electronic components. In addition, the anisotropy of the thermal conductivity is too large and the thermal conductivity in the non-oriented direction is extremely low, resulting in a low total thermal conductivity and insufficient heat dissipation.
[0017] Patent Document 5 describes a thermally conductive sheet comprising a sheet-like rubber-like elastomer and fibrous carbon embedded obliquely to the thickness direction of the rubber-like elastomer, the fibrous carbon being amorphous carbon fiber with both ends exposed on the surface of the rubber-like elastomer.
[0018] However, the fibrous carbon used in Patent Document 5 is not the "carbon nanofiber (CNF) defined by size" described above, and cannot be used in narrow parts of electronic components, etc., and the anisotropy of thermal conductivity is too large, and the thermal conductivity in the non-oriented direction is extremely low, resulting in a low total thermal conductivity and insufficient heat dissipation. Furthermore, the electrical conductivity is high, making it unsuitable as a heat dissipation material for electronic components. [Prior art documents] [Patent documents]
[0019] [Patent Document 1] JP 2012-188790 A [Patent Document 2] JP 2017-066546 A [Patent Document 3] JP 2013-131563 A [Patent Document 4] JP 2022-127596 A [Patent Document 5] JP 2023-042619 A Summary of the Invention [Problem to be solved by the invention]
[0020] The present invention has been made in consideration of the above-mentioned background technology, and an object of the present invention is to provide a thermally conductive structure containing fibrous carbon, which has a small anisotropy of thermal conductivity and has excellent overall thermal conductivity. In addition, by developing and adopting carbon nanofiber (CNF), which has extremely good dispersibility, as the fibrous carbon contained in the thermally conductive structure, it is possible to provide a thermally conductive structure that has various excellent physical properties, including non-conductivity. [Means for solving the problem]
[0021] As a result of extensive research to solve the above problems, the inventors have found that only by using a specific fibrous carbon as a raw material and performing wet grinding can carbon nanofibers with specific sizes and distribution be made into a state in which they can be isolated approximately one by one, or a group of carbon nanofibers in a dispersed or dispersible state approximately one by one be obtained, and that this fibrous carbon is suitable for inclusion in a thermally conductive structure.
[0022] Furthermore, the inventors discovered that if the carbon nanofiber group is used in combination with an isotropic thermally conductive filler and dispersed in a base resin, a relatively high thermal conductivity can be achieved not only in the orientation direction of the carbon nanofiber (CNF) but also in the non-orientation direction, as compared with other fibrous carbons, and thus completed the present invention. Furthermore, since sufficient properties are exhibited even with a small amount of the compound, the thermally conductive structure containing the compound becomes a non-conductive material.
[0023] That is, the present invention provides a thermally conductive structure comprising a base material, a group of carbon nanofibers, and an isotropic thermally conductive filler, The carbon nanofiber group is obtained by wet grinding pitch-based fibrous carbon as a raw material, and is characterized in that "50% or more of the total number of carbon nanofibers are distributed in the range of 30 nm to 1000 nm in diameter and 0.2 μm to 70 μm in length." This thermally conductive structure is characterized in that the carbon nanofiber group is obtained by wet grinding pitch-based fibrous carbon as a raw material.
[0024] The present invention also provides the above-mentioned thermally conductive structure, wherein the carbon nanofibers contained in the carbon nanofiber group have a number average aspect ratio of 3 or more and 200 or less.
[0025] The present invention also provides the above-mentioned thermally conductive structure, in which the carbon nanofibers contained in the carbon nanofiber group have a number average diameter of 30 nm or more and 1000 nm or less, and a number average length of 0.2 μm or more and 70 μm or less.
[0026] The present invention also provides the above-mentioned thermally conductive structure, wherein the pitch-based fibrous carbon as a raw material is mesophase pitch-based fibrous carbon.
[0027] The present invention also provides the above-mentioned thermally conductive structure, wherein the mesophase pitch fibrous carbon as the raw material is a random type mesophase pitch fibrous carbon.
[0028] The present invention also provides the thermally conductive structure as described above, wherein the wet pulverization is bead mill pulverization or ball mill pulverization carried out in an aqueous medium in the presence of a surfactant.
[0029] The present invention also provides the thermally conductive structure, wherein the carbon nanofiber group is obtained by dry-pulverizing pitch-based fibrous carbon until the raw material has a number average length of 100 μm or less, and then wet-pulverizing the same.
[0030] The present invention also provides the above-mentioned thermally conductive structure, wherein the isotropically thermally conductive filler is a metal oxide, a nitride, a metal carbide, a metal hydroxide, a metal carbonate, or a semi-metal.
[0031] The present invention also provides the thermally conductive structure as described above, wherein the isotropic thermally conductive filler has a thermal conductivity at 300 K of 5 [W / (m·K)] or more.
[0032] The present invention also provides the thermally conductive structure as described above, wherein the isotropic thermally conductive filler has a thermal conductivity at 300 K of 600 [W / (m·K)] or less.
[0033] The present invention also provides the above-mentioned thermally conductive structure, in which the above-mentioned carbon nanofiber group containing "carbon nanofibers substantially free of mixed resin" is contained in a base material.
[0034] The present invention also provides the above-mentioned thermally conductive structure, in which "a group of carbon nanofibers from which the mixed resin present in the raw material has been removed by carrying out a heat treatment prior to the wet grinding" is contained in a base material.
[0035] The present invention also provides the thermally conductive structure, wherein the carbon nanofiber groups are contained in an amount of 1.0 vol % to 20 vol % based on the entire thermally conductive structure.
[0036] The present invention also provides the thermally conductive structure described above, wherein the isotropic thermally conductive filler is contained in an amount of 20% by volume or more and 85% by volume or less based on the entire thermally conductive structure.
[0037] The present invention also provides the above-mentioned thermally conductive structure, which is non-conductive.
[0038] The present invention also provides a molded body, a coating film, a sheet, or an adhesive layer, which is characterized by being the above-mentioned thermally conductive structure.
[0039] The present invention also provides an adhesive, a coating material, or a composition for preparing a thermally conductive structure, characterized in that it comprises the above-mentioned composition for the thermally conductive structure. Effect of the Invention
[0040] The thermally conductive structure of the present invention contains carbon nanofibers (CNFs) which have a smaller particle size than carbon milled fibers (CMFs) and are therefore suitable for inclusion in thermally conductive structures in terms of particle size; have a large aspect ratio; and despite this, have extremely good dispersibility, so that the thermal conductivity can be increased (as a whole) in both the oriented and non-oriented directions.
[0041] In the present invention, "fibrous carbon" refers to any long and thin carbonaceous material (carbon material) having a graphite structure, and includes carbon fiber, carbon nanofiber, carbon milled fiber, and carbonaceous materials (carbon materials) of similar size, etc. In addition, "fibrous carbon" includes filaments of carbonaceous materials (carbon materials) having a graphite structure, elementary filaments constituting the filaments, strands in which the filaments are arranged vertically in parallel, etc.
[0042] Hereinafter, carbon nanofibers and carbon nanofiber groups may be abbreviated simply as "CNF." Furthermore, carbon milled fiber and the carbon milled fiber group may be abbreviated simply as "CMF." Furthermore, carbon nanotubes and carbon nanotube groups may be abbreviated simply as "CNT."
[0043] The present invention has made it possible to provide a thermally conductive structure that is excellent in thermal conductivity, non-conductivity, dispersibility, etc., by developing CNF, which has a high aspect ratio and excellent dispersibility, as the fibrous carbon to be contained in the thermally conductive structure.
[0044] According to the present invention, the above problems and issues are resolved, and CNFs with a large aspect ratio, such as a diameter of 30 nm or more and 1000 nm or less and a length of 0.2 μm or more and 70 μm or less, can be made into a state in which they can be isolated approximately one by one, or dispersed or dispersible approximately one by one. In the commonly known fibrous carbon in the broad sense, multiple CNFs are tightly bound to the surroundings to form a single unit. Conventionally, it has not been possible to separate or peel off CNFs while maintaining a high aspect ratio. In other words, it was impossible to produce CNF by grinding or other processes while maintaining a high aspect ratio, and to make it reproducibly and stably in a state that could be isolated (separated) or (re)dispersed without causing aggregation.
[0045] The above is possible by using the CNF of the present invention. The thermally conductive structure of the present invention has various excellent properties due to the good dispersion state of the CNF. For example, it can be dispersed in a wide range of concentrations while maintaining a good dispersion state in the base material, resulting in high thermal conductivity.
[0046] In the present invention, by using a specific fibrous carbon as the raw material and making wet grinding essential, it is possible to obtain a group of carbon nanofibers with specific size and distribution, and structures in which these are dispersed can exhibit a variety of excellent properties.
[0047] In addition, by further limiting the type of fibrous carbon used as the raw material, further limiting the dry grinding method and / or the wet grinding method, or further limiting the manufacturing method by adding specific substances or manufacturing processes, the performance of CNF, such as its dispersibility, can be further improved, thereby improving performance such as high thermal conductivity, high non-conductivity, and high ease of processing.
[0048] With regard to thermal conductivity, there are few substances with an average particle size of less than 5 μm, a high aspect ratio, and high thermal conductivity. For example, carbon nanotubes (CNTs) are one candidate, but they have poor dispersibility and orientation and have not yet been put to practical use. Additionally, various types of whiskers (metal, inorganic single crystal, etc.) are also considered as candidates, but because it is difficult to produce whiskers with good dispersibility and orientation, they have not yet been widely put to practical use.
[0049] According to the thermally conductive structure of the present invention, the (average) particle size contained in the structure can be made small (since it is small), so that the thermally conductive structure can be used in narrow parts of electronic components, etc. If fibrous carbon such as CMF having a length of about 100 μm is contained, the thermally conductive structure is difficult to use in narrow parts.
[0050] In conventional techniques that do not pulverize fibrous carbon or that use fibrous carbon other than "CNF in the present invention" such as CMF, even if pulverized fibrous carbon is used, the thermal conductivity in the orientation direction is improved, but problems with the diameter, length, rigidity, etc. have occurred, for example, as described below. The thermally conductive structure of the present invention eliminates the following problems.
[0051] Fibrous carbon such as CNT and CNF other than "the CNF of the present invention" is difficult to knead, but the CNF of the present invention has good dispersibility and is easy to knead. Fibrous carbon such as CMF has difficulty in cutting when processed into a sheet, but the thermally conductive structure of the present invention in which CNF is dispersed has excellent cuttability and can be easily formed into a sheet. For long fiber types such as CMF, the condition for high performance is that the cut surfaces are exposed, but according to the present invention, it is not necessary for the CNF to be exposed. In conventional techniques, fibrous carbon cannot be used as a thermoelectric conductive material in narrow spaces due to restrictions imposed by its length and diameter, but according to the present invention, it can be used even in narrow spaces. Materials using long fibers such as CMF are difficult to extrude from a nozzle, etc., and are not suitable for processing such as filling, coating, and molding, but the thermally conductive structure of the present invention is excellent in manufacturability and processability.
[0052] The thermally conductive structure of the present invention has little difference in "various performances" between the non-oriented and oriented directions of the CNFs and has excellent thermal conductivity overall. Therefore, due to the high thermal conductivity even in the non-oriented direction, the thermally conductive structure also has excellent thermal conductivity in the thickness direction, which is the non-oriented direction, even if it is in sheet form. Furthermore, the thermally conductive structure of the present invention is non-conductive despite its high thermal conductivity.
[0053] In this specification, "non-conductive" means a material having a volume resistivity of 1.0×10 ―1 [Ω cm] or more, and preferably 1.0×10 0 [Ω cm] or more, and particularly preferably 1.0×10 2 This refers to more than [Ω·cm].
[0054] As described above, according to the thermally conductive structure of the present invention, the thermal conductivity is low in the oriented direction and non-oriented direction of the contained CNFs, but strictly speaking, the values are different, so it is possible to further improve performance and differentiate the structure by utilizing this anisotropy. However, in general, the anisotropy is not as high as that of CMFs that are strongly oriented in the base material; in other words, the thermal conductivity in the non-oriented direction is also high, and the overall thermal conductivity is high, so that an excellent thermally conductive structure (a structure with excellent heat dissipation properties) can be provided. Furthermore, it has been found that even for flat structures such as coatings, sheets, adhesive layers, etc., high thermal conductivity not only in the vertical direction (thickness direction) but also in the horizontal direction is effective in increasing overall thermal conductivity and heat dissipation.
[0055] CNF has a smaller specific gravity than, for example, metals or those containing other thermally conductive materials as mentioned above, so it is possible to ultimately reduce the weight of the thermally conductive structure.
[0056] The thermally conductive structure of the present invention exhibited a thermal conductivity that was 1.2 times or more higher than that of a structure containing only an isotropic thermally conductive filler such as an inorganic filler without adding CNF.
[0057] Conventionally, long fibers have generally been strongly oriented in one dimension to obtain their performance, but in the thermally conductive structure of the present invention, the CNFs in the present invention are also oriented in three dimensions (since they tend to have an orientation direction), so the ratio of oriented directions to non-oriented directions can be made 2 or less, and the structure shows high thermal conductivity and heat dissipation properties overall. Furthermore, it exhibits excellent non-conductivity. In particular, since sufficient properties are exhibited even with a small amount of CNF blended, the thermally conductive structure of the present invention is non-conductive. [Brief description of the drawings]
[0058] [Figure 1] Scanning electron microscope (SEM) photographs of the cross section of the raw material pitch-based fibrous carbon before grinding. (Left) Radial mesophase pitch-based fibrous carbon (middle) Random mesophase pitch-based fibrous carbon (right) Onion mesophase pitch-based fibrous carbon [Diagram 2] Schematic diagrams of cross sections of pitch-based fibrous carbon. (a) (a') Random type mesophase pitch-based fibrous carbon, (b) radial type mesophase pitch-based fibrous carbon, and (c) onion type mesophase pitch-based fibrous carbon. [Diagram 3] 1 is a scanning electron microscope (SEM) photograph of the cross section of one random mesophase pitch-based fibrous carbon preferably used as a raw material. [Figure 4] These are scanning electron microscope (SEM) photographs of random mesophase pitch-based fibrous carbon (before crushing), which is preferably used as a raw material. (a) 400x (b) 1300x [Diagram 5] 1 is a scanning electron microscope (SEM) photograph of fibrous carbon after dry grinding in the present invention. (a) 600x (b) 1500x [Figure 6] FIG. 2 is a 700x optical microscope (biological microscope) photograph showing the process of wet grinding in the present invention (reference drawing). [Figure 7] 1 is a scanning electron microscope (SEM) photograph of the present invention after wet grinding. (a) 1500x (b) 6500x [Figure 8] FIG. 1 is a schematic diagram showing a manufacturing process for filaments of (random type) mesophase pitch-based fibrous carbon preferably used as a raw material. [Figure 9] FIG. 1 is a schematic diagram showing an example of an apparatus used for dry grinding in the present invention. [Figure 10] 1 is a bar graph showing the increase in thermal conductivity when the base material is a curable silicone resin and four types of isotropic thermally conductive fillers (alumina, aluminum nitride, silicon metal, silicon carbide) are each mixed with 5 volume % of the carbon nanofiber group (CNF) of the present invention relative to the entire thermally conductive structure. [Figure 11] 1 is a bar graph showing the increase in thermal conductivity and the difference (increase) in the difference (ratio) between the thermal conductivity in the non-oriented direction and the oriented direction when the base material is a cured silicone resin, the isotropic thermally conductive filler is alumina, and the carbon nanofiber group (CNF) of the present invention is contained in place of the CNF, and other thermally conductive substances (carbon milled fiber (CMF), aluminum nitride) are used. [Figure 12] 1 is a line graph showing that when the base material is a curable silicone resin, the isotropic thermally conductive filler is alumina, and the carbon nanofiber group (CNF) of the present invention is contained in varying amounts, the thermal conductivity in the non-oriented direction also increases. [Figure 13] 1 is a line graph showing that when the base material is a curable silicone resin, the isotropic thermally conductive filler is alumina, and various amounts of aluminum nitride are included instead of the carbon nanofibers (CNF) of the present invention, there is no change in thermal conductivity and no difference in the (change in) thermal conductivity between the non-oriented direction and the oriented direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0059] The present invention will be described below, however, the present invention is not limited to the specific embodiments below and can be modified as desired within the scope of the technical concept.
[0060] The thermally conductive structure of the present invention is characterized in that it is made from pitch-based fibrous carbon as a raw material and is wet-pulverized to obtain "a group of carbon nanofibers having a diameter of 30 nm or more and 1000 nm or less, and 50% or more of the total being distributed in the range of a length of 0.2 μm or more and 70 μm or less," which is contained in a base material together with an isotropic thermally conductive filler.
[0061] [Carbon nanofibers] The carbon nanofiber group in the present invention has a diameter of 30 nm or more and 1000 nm or less, and a length of 0.2 μm or more and 70 μm or less, with 50% or more of the total number of the carbon nanofiber group being distributed in that range. It is essential that 50% or more of the total particles are distributed within the above range, but preferably 70% or more, more preferably 80% or more, even more preferably 90% or more, particularly preferably 95% or more, and most preferably 98% or more. According to the CNF manufacturing method of the present invention, it is possible to produce CNFs with the above-mentioned number percentage or more. Therefore, in consideration of dispersibility and the properties of the structure containing the CNF, the sharper the distribution, the better, but in consideration of productivity, etc., a broader distribution is also acceptable.
[0062] The diameter of CNF having the above distribution is 30 nm or more and 1000 nm or less, preferably 50 nm or more and 900 nm or less, more preferably 100 nm or more and 850 nm or less, even more preferably 300 nm or more and 800 nm or less, and particularly preferably 500 nm or more and 750 nm or less. The same applies to the number average diameter of the CNFs in the present invention.
[0063] According to the method for producing CNF of the present invention, CNFs with diameters within the above range can be produced with high yield. If the diameter is too small, production may be difficult, dispersion may be difficult, and the length may also be too short, resulting in a small aspect ratio. On the other hand, if the diameter is too large, the performance of the thermally conductive structure may be poor, or the structure may be difficult to manufacture.
[0064] The length of the CNF having the above distribution is from 0.2 μm to 70 μm, preferably from 0.5 μm to 50 μm, more preferably from 1 μm to 40 μm, even more preferably from 2 μm to 30 μm, and particularly preferably from 4 μm to 20 μm. The number average length of the CNF in the present invention is the same as above.
[0065] According to the method for producing CNF of the present invention, CNFs having lengths within the above range can be produced with good yield. If the length is too short, the aspect ratio may become small, the performance (thermal conductivity, etc.) in the thermal conductive structure may be poor, it may become difficult to prevent the CNF from agglomerating, or it may become difficult to produce the CNF. On the other hand, if the length is too long, various performance properties of the CNF may be inferior, the uses (places of application, etc.) of the thermally conductive structure may be limited, or it may become difficult to manufacture while maintaining a large aspect ratio.
[0066] The CNF that can be isolated and dispersed in the present invention has a diameter and length within the above ranges (the above ranges are preferable), and is therefore characterized by a large aspect ratio. The number average aspect ratio of the CNF in the present invention is preferably 3 or more and 200 or less, more preferably 5 or more and 160 or less, still more preferably 7 or more and 130 or less, particularly preferably 15 or more and 100 or less, and most preferably 20 or more and 70 or less.
[0067] If the number average aspect ratio is too small, high thermal conductivity may not be obtained, the performance of the thermally conductive structure (e.g., molded body, coating film, adhesive layer, etc.) may be inferior, or the application areas may be limited. On the other hand, if the number average aspect ratio is too large, it may become difficult to manufacture the CNF or to disperse it.
[0068] When pitch-based fibrous carbon is used as the raw material, and preferably dry-milled and then wet-milled, the raw fibrous carbon is specifically and neatly split vertically during milling; in other words, the raw filament can be suitably peeled off from the filament without shortening its length too much. As a result, the present invention has produced CNFs with a suitable aspect ratio that has never been seen before. It is believed that the large aspect ratio and suitable size and shape have improved the physical properties, such as thermal conductivity and non-conductivity, of structures containing the CNFs.
[0069] The diameter and length of the carbon nanofibers contained in the carbon nanofiber group produced by the present invention are determined by randomly selecting 100 fibers, measuring the diameter and length of each fiber, and taking the arithmetic mean using an optical microscope or a scanning electron microscope (SEM). The optical microscope is preferably equipped with a gauge for size measurement in order to improve measurement accuracy and reduce measurement time. When it is difficult to measure without increasing the magnification, a scanning electron microscope (SEM) (photograph) is used.
[0070] Since the CNF in the present invention has a large aspect ratio, the diameter and length of each fiber are measured using a microscope rather than using a particle size distribution meter. Since an automatic particle size distribution meter cannot suitably measure the diameter and length, the above method is the only option. In the present invention, size values such as diameter, length, number average aspect ratio, etc. are defined as those measured as described above.
[0071] When the CNF of the present invention is contained or dispersed in a base material such as a base resin, it may be contained in the form of a solid (powder) or may be contained first as a dispersion liquid. When they exist as solids (powder), for example, the CNFs are in a state where they can be isolated one by one or dispersed one by one, as shown in Figure 7. When they exist in a structure or dispersion, the CNFs are in a dispersed state. In addition, the CNF in the present invention is not necessarily capable of being separated into individual raw filaments as described below, but it is sufficient if the CNF can be dispersed individually. The CNF in the present invention can be made to have the dispersibility and dispersed state described above.
[0072] <Production of carbon nanofibers> The CNFs of the present invention having the above-mentioned shape (diameter and length) and distribution are obtained by at least wet grinding, preferably by dry grinding followed by wet grinding.
[0073] Furthermore, by using a specific type of fibrous carbon as the raw material, it is possible to obtain (re)dispersible CNFs having the above-mentioned shape and distribution. It is also preferable to add other treatments (operations) as necessary before the dry milling, between or during the dry milling and the wet milling, or after the wet milling. Moreover, the above-mentioned preferable dry milling and the above-mentioned essential wet milling may each be carried out in one stage or two or more stages.
[0074] "CNF obtained by using pitch-based fibrous carbon as a raw material and subjecting it to wet grinding (preferably after dry grinding)" can be dispersed at a high concentration in a base material such as a base resin, and the thermally conductive structure dispersed at such a high concentration has the excellent physical properties described above and below. However, a "more preferred manufacturing process" in the present invention is shown below. In addition, when the following processes are carried out, it is particularly preferable to carry out the production process in the following order: preparation of raw material fibrous carbon, pre-grinding, dry grinding, heat treatment, moistening treatment, wet grinding, aggregation prevention treatment, and water removal treatment.
[0075] Of the above, at least the preparation of a specific raw material fibrous carbon and the wet pulverization are essential, and if so, the thermally conductive structure, molded body, coating film, adhesive layer, sheet, etc. of the present invention can be produced. Of the above, none of the pre-grinding, dry grinding, heat treatment, wetting treatment, aggregation prevention treatment, and water removal treatment is essential, but in order to produce the toner satisfactorily, it is preferable to carry out some or all of them as necessary. In particular, the "heat treatment" is preferably carried out when the raw material contains a resin such as a sizing material, but does not have to be carried out when the raw material has not been subjected to a sizing treatment or the like. It is particularly preferable to carry out "dry grinding". Each processing step will be described below in order of processing.
[0076] <<Raw material fibrous carbon>> In the present invention, it is essential to use pitch-based fibrous carbon as the fibrous carbon before grinding (raw material fibrous carbon), but it is preferable to use mesophase pitch-based fibrous carbon, and it is particularly preferable to use random mesophase pitch-based fibrous carbon. No matter what grinding method is used for PAN-based fibrous carbon, it is not possible to obtain CNFs having a diameter of 30 nm or more and 1000 nm or less and a length of 0.2 μm or more and 70 μm or less that have the high number average aspect ratio described above.
[0077] Furthermore, even if the pitch-based fibrous carbon is isotropic pitch-based fibrous carbon, it may be difficult to obtain carbon nanofibers having the above-mentioned size, shape, and distribution.
[0078] On the other hand, mesophase pitch-based fibrous carbon is classified at least into radial type (Figure 1 (left), Figure 2 (b)), random type (Figure 1 (center), Figure 2 (a) (a'), Figure 3), and onion type (Figure 1 (right), Figure 2 (c)) based on its cross-sectional shape (i.e., internal shape). The "random type" is one in which the fiber cross section is random. For this reason, it was named random type.
[0079] In the present invention, even if mesophase pitch-based fibrous carbon is used, it may be somewhat difficult to obtain carbon nanofibers having the above size, shape, and distribution when radial type mesophase pitch-based fibrous carbon or onion type mesophase pitch-based fibrous carbon is used. When radial or onion type fibrous carbon is used as the raw material, it may not be possible to obtain the above-mentioned shape, form, and distribution, and in particular, it may not be possible to obtain CNF with a large number average aspect ratio (for example, only CNF with a number average aspect ratio of less than 3 may be obtained).
[0080] The "filaments constituting the random mesophase pitch fibrous carbon" are made up of smaller rod-shaped or plate-shaped (sheet-shaped) filaments. For example, in Figure 3, plate-shaped (sheet-shaped) filaments are vertically assembled. In this specification, the "smaller rod-shaped or plate-shaped (sheet-shaped) objects" that make up the filaments are abbreviated as "elementary filaments." It is thought that within a single elementary filament, graphite structures made up of condensed benzene rings are stacked together in the same direction to form a single filament.
[0081] In the present invention, the fibrous carbon raw material has a number average thickness or number average thickness of the elementary filaments constituting the filament, which is preferably 10 nm or more and 200 nm or less, more preferably 15 nm or more and 150 nm or less, further preferably 20 nm or more and 100 nm or less, and particularly preferably 30 nm or more and 70 nm or less.
[0082] When the size of the raw filaments of the fibrous carbon raw material is equal to or greater than the above lower limit, the thermal conductivity [W / (m·K)] of the filaments containing the raw filaments increases rapidly, and the "various thermal properties including thermal conductivity" of the thermally conductive structure containing CNF containing the raw filaments are also improved. On the other hand, when it is equal to or less than the upper limit, it is easy to prepare "filament or fibrous carbon" containing such elementary filaments as a raw material.
[0083] Fig. 8 shows an outline of the manufacturing process of mesophase pitch-based fibrous carbon filament 10. Random type mesophase pitch-based fibrous carbon 1 can also be obtained by adjusting the spinning viscosity, nozzle shape, flow state of the raw material pitch, etc. in Fig. 8. There is no stretching process in the manufacturing process of mesophase pitch-based fibrous carbon. The microstructure controlled in the spinning process becomes the crystal structure of the filament 10 almost as it is, and a boundary where the crystal structure orientation differs is formed, and the raw filament 20 becomes visible (exists).
[0084] In Figure 8, the thickness of the raw material filament 10 is usually 4000 nm to 10000 nm, and often 5000 nm to 7000 nm. On the other hand, the number average thickness or number average thickness of the raw filaments 20 in the raw material fibrous carbon filament 10 in the present invention is preferably 10 nm or more and 200 nm or less, and more preferably 15 nm or more and 100 nm or less, so that in the raw material fibrous carbon, there are usually 40 to 700 raw filaments 20, and in most cases 60 to 400 raw filaments 20, in one filament 10. When one elementary filament 20 is divided (defined) at a boundary where the orientation of the crystal structure is different, the above number of elementary filaments 20 are bundled together to form one filament 10. Note that in Fig. 8, for ease of viewing, it is depicted as if one filament were made up of three elementary filaments when viewed from the front.
[0085] In the present invention, when random mesophase pitch-based fibrous carbon is used as the raw material, it is particularly preferable that the carbon fiber has the above-mentioned form, although there is no limitation thereto. The shape, distribution, etc. of the carbon nanofibers in the present invention, as well as whether or not such carbon nanofibers can be formed in the first place, are largely dependent on the type of fibrous carbon used as the raw material.
[0086] <<<Relationship between the carbon nanofiber of the present invention and the raw filament>>> The carbon nanofibers produced by the present invention are preferably configured by gathering together 2 to 20 "bare filaments constituting the raw material filament," more preferably 3 to 16, and particularly preferably 4 to 12. The number of raw filaments is the average value for each carbon nanofiber in the carbon nanofiber group. When producing carbon nanofibers, the crystallinity and external shape of the filaments may be slightly deformed, but this is also included in the above-mentioned "number of filaments." Even if the filaments are originally plate-shaped, they become elongated after being crushed, and are therefore referred to as the "number of filaments" as above.
[0087] <<Pre-grinding>> The fibrous carbon as the raw material may be in the form of chopped fiber or milled fiber, but is preferably in the form of chopped fiber. In the case of milled fiber, many short fibers with a length of about 1 μm are mixed in, so chopped fiber is preferable in order to obtain carbon nanofibers with a large aspect ratio. In the case of milled fiber, for example, even if it is said that the "average length is 70 μm," many short fibers with a length of about 1 μm may be mixed in.
[0088] Although not limited, the fibrous carbon as the raw material in the pre-pulverization is preferably 1 mm to 15 mm on average, more preferably 2 mm to 10 mm, and particularly preferably 5 mm to 8 mm. For example, in the case of a long fiber bobbin type, pre-pulverization may be necessary. If the size is within the above range from the beginning, it is preferable not to perform pre-pulverization.
[0089] The grinding method for the pre-grinding is not particularly limited, and any commercially available dry grinding machine can be used, for example, a cutter mill or the like can be used as the device.
[0090] <<Dry grinding>> The dry grinding in the present invention is preferably airflow grinding, cutter grinding, or "grinding in which both airflow grinding and cutter grinding are performed simultaneously." "Grounding in which both airflow grinding and cutter grinding are performed simultaneously" means "grinding that has both an airflow grinding mechanism and function and a cutter grinding mechanism and function at the same time."
[0091] <<<Airflow grinding>>> Examples of the airflow pulverization include pulverization using an airflow pulverizer such as a cyclone mill, and a jet mill. Airflow pulverization using a cyclone mill produces an airflow by rotating an impeller (rotating blade) and pulverizes the object thrown into the airflow in a dry state to produce fine particles, while airflow pulverization using a jet mill produces fine particles by colliding the object with a collision plate in a dry state to pulverize the object. In order to obtain carbon nanofibers of a predetermined shape by wet grinding, an airflow grinder having a rotating body such as an impeller, rotor, blade, or rotary blade (such as a jet mill) or a grinder described later in <<Grinding that performs both airflow grinding and cutter grinding simultaneously>>> is preferable as the "dry grinding before wet grinding".
[0092] As the cyclone mill, commercially available devices can be suitably used, such as Super Powder Mill manufactured by Nishimura Machinery Works, Ltd., Tornado Mill manufactured by Sansho Industry Co., Ltd., and Dream Mill (registered trademark) manufactured by Furukawa Industrial Machinery Systems Co., Ltd.
[0093] The structure of the cyclone mill is not particularly limited, but it is particularly preferred that the cyclone mill has one or more impellers and crushes the materials to be crushed by mainly colliding them with each other using a swirling air current generated by the impeller, because this makes it easier to achieve the effects of using the air current crusher, there is very little metal contamination, etc.
[0094] As the jet mill, commercially available devices can be suitably used, for example, from Seishin Enterprise Co., Ltd., Hosokawa Micron Corporation, Nippon Pneumatic Co., Ltd., and Nisshin Engineering Inc.
[0095] <<<Cutter-type crushing>>> Examples of cutter-type pulverization include pulverization using a crusher mill, a pin mill, a cutter mill, a hammer mill, an axial flow mill, and the like.
[0096] <<<Simultaneous airflow and cutter grinding>>> As the dry pulverization in the present invention, pulverization in which both airflow pulverization and cutter pulverization are carried out simultaneously is particularly preferred. In particular, the dry grinding in the present invention is preferably carried out using a dry grinder having a blade and capable of applying shear and impact, or is preferably carried out using a dry grinder that applies "shear and impact by a blade". A schematic diagram of an example of such a dry grinding mill is shown in FIG.
[0097] When dry grinding is performed using a "full airflow grinder that does not use an impeller, etc." such as a jet mill, cyclone mill, tornado mill, or Dream Mill (registered trademark), the aspect ratio may become too small (the shape may become round) in the subsequent wet grinding.
[0098] The ambient temperature or set temperature in dry grinding is not particularly limited and may be in accordance with the method of use of the device used, but is preferably 0°C or higher and 50°C or lower, and particularly preferably 5°C or higher and 35°C or lower. The impeller rotation speed may also be determined in accordance with the method of use of the device used, but is preferably 4,000 rpm or more and 20,000 rpm or less, and particularly preferably 8,000 rpm or more and 15,000 rpm or less.
[0099] Using the above-mentioned apparatus and the above-mentioned crushing method, the powder is dry-pulverized until the number average length becomes 100 μm or less, and then the powder is subjected to the next step. By dry-pulverizing the CNF until it is 100 μm or less and then wet-pulverizing it, the diameter, length, (number average) aspect ratio, shape distribution, etc. of the CNF tend to fall within the required or preferred ranges described above.
[0100] The number average length is preferably adjusted to 100 μm or less by dry grinding, more preferably 5 μm to 70 μm, further preferably 7 μm to 50 μm, and particularly preferably 10 μm to 40 μm. If the number average length after dry grinding is too long, it may be difficult to achieve a final diameter and length of the carbon nanofiber within the above-mentioned range in the subsequent wet grinding step, even if the conditions for the wet grinding are adjusted. On the other hand, if the length after dry pulverization is too short, the length of the carbon nanofibers after wet pulverization cannot be longer than that, and therefore it may be difficult for the final length and number average aspect ratio of the carbon nanofibers to fall within the above-mentioned preferred ranges, etc. In particular, the aspect ratio of the final carbon nanofibers may be too small.
[0101] Regarding the number average diameter after dry milling, it is difficult to make it small by dry milling alone, that is, it is difficult to mill so as to increase the aspect ratio. Furthermore, if the diameter is forcibly reduced by dry milling, the length also becomes shorter, and it becomes difficult to keep the final aspect ratio after wet milling within a suitable range. The diameter after dry pulverization is preferably 3000 nm or more, more preferably 5000 nm to 15000 nm, and particularly preferably 7000 nm to 12000 nm. It is desirable to carry out dry pulverization so that the diameter falls within this range.
[0102] The number average aspect ratio after dry grinding is not particularly limited, but is preferably 10 or less, more preferably 1.2 or more and 7 or less, and particularly preferably 1.5 or more and 5 or less. By dry grinding, it is difficult to increase the number average aspect ratio above the upper limit, i.e., it is difficult to reduce the average fiber diameter to a degree that allows the number average aspect ratio to be increased above the upper limit. In the present invention, the number average length is preferably set to 100 μm or less by dry grinding, and a relatively large diameter and a relatively small number average aspect ratio are obtained, or by doing so, the subsequent wet grinding can finally produce CNFs with the suitable "diameter, length, and large number average aspect ratio" as described above.
[0103] <<Heat treatment>> The thermally conductive structure of the present invention is preferably one in which "CNF substantially free of mixed resins" is contained in the base material. Here, the mixed resin may be, for example, a case where a sizing agent or the like is contained in the fibrous carbon as a raw material. That is, the mixed resin is not limited, but may be, for example, a sizing agent or the like.
[0104] In the present invention, when the dry-pulverized product contains a resin, it is preferable to remove the resin by carrying out a heat treatment. In other words, the thermally conductive structure of the present invention is preferably one in which the base material contains CNFs in a state in which the resin contained in the raw fibrous carbon has been removed by carrying out a heat treatment before the above-mentioned wet-pulverization. When the raw material fibrous carbon does not contain any resin such as a sizing agent, the heat treatment can be omitted.
[0105] The heat treatment conditions are not limited, but for example, the material is heated in a furnace at a temperature of 320° C. to 480° C. for 5 to 15 minutes, and the resin content is reduced to preferably 0.1 mass % or less, particularly preferably 0.01 mass % or less. By carrying out the heat treatment, preferably after dry grinding and before wet grinding, the grinding and dispersion effects of the wetting agent or surfactant used in the subsequent wet treatment or wet grinding step (if wet treatment is carried out) are improved.
[0106] <<Wet processing>> Although not limited thereto, it is preferable to further carry out a moistening treatment, and although not limited thereto, it is particularly preferable to carry out a moistening treatment after the dry grinding or heat treatment. The wet treatment is preferably carried out by immersing the product obtained above in an aqueous solution containing an anionic surfactant, a cationic surfactant, or an amphoteric surfactant, which can also be suitably used in the subsequent wet grinding.
[0107] The anionic surfactant is preferably a polymeric anionic surfactant ("polymer" also includes oligomers), and more preferably an alkali metal salt, ammonium salt, alkylammonium salt, alkylolammonium salt, phosphate ester, or the like, of a (co)polymer having an acid group. The above-mentioned anionic surfactants may be used alone or in combination of two or more kinds.
[0108] The above-mentioned "(co)polymer having an acid group" is particularly preferably at least one (co)polymer selected from the group consisting of (co)polymers of (meth)acrylic acid, (co)polymers of (anhydride) phthalic acid, (co)polymers of vinylbenzenesulfonic acid, and (co)condensates of naphthalenesulfonic acid. Here, the terms "(co)", "(meth)", and "(anhydride)" include both the presence and absence of parentheses. In the case of copolymers, the copolymerizing monomer is not particularly limited, and examples thereof include (meth)acrylic acid alkyl esters, (meth)acrylic acid hydroxyalkyl esters, styrene, vinyl acetate, and the like. The (co)condensation product of naphthalenesulfonic acid includes a product in which the ring is bonded with an aldehyde such as formaldehyde. In the case of the co-condensation product, the co-condensation monomer includes phenol, cresol, naphthol, etc.
[0109] In addition, the cationic surfactant is preferably a surfactant in which a quaternary ammonium is a hydrophilic group, and the "N" of the quaternary ammonium is + The substituent on " is not particularly limited, but preferable are alkyl groups (which may have a substituent) such as stearyl group, palmityl group, dodecyl group, methyl group, benzyl group, butyl group, etc. Also, it is desirable to use a long-chain alkyl group having preferably 6 or more carbon atoms, particularly preferably 12 or more carbon atoms. The counter anion is not particularly limited, but a halogen ion such as a chloride ion or a bromide ion is particularly preferred.
[0110] Examples of amphoteric surfactants include alkyl betaine type, fatty acid amidopropyl betaine type, alkyl imidazole type, amino acid type, and amine oxide type.
[0111] Among these, it is preferable to use an anionic surfactant or an amphoteric surfactant. The content of the surfactant and the content of the fibrous carbon in the aqueous dispersion medium (after dry grinding) are within the same numerical ranges as those for <wet grinding> described below.
[0112] The use of a surfactant, and in particular the use of the preferred anionic or amphoteric surfactants described above, has the effect of unraveling the fibrous carbon vertically, allowing the diameter to be narrowed while maintaining a long length, resulting in carbon nanofiber(s) with a large average aspect ratio.
[0113] <<Wet grinding>> In the present invention, it is essential to carry out wet milling after dry milling. The wet milling is not particularly limited, but is preferably bead mill milling or ball mill milling. Bead mill milling or ball mill milling carried out in an aqueous medium in the presence of a surfactant is particularly preferred. Between the dry milling and the wet milling, the above-mentioned "other treatments" such as heat treatment and wet treatment may be performed. The "other treatments" further include premixing, preliminarily preparing a solution, and the like.
[0114] The surfactant may be any of those described in the <Wetting Treatment> section above, whether or not the wetting treatment has been performed. The same surfactants are also preferred. That is, as described above in the section on <Wet Treatment>, anionic surfactants, cationic surfactants, or amphoteric surfactants are preferred. The surfactant used in the wet treatment may be used as is in the wet grinding, or a new surfactant may be added or a different surfactant from that used in the wet treatment may be added during the wet grinding.
[0115] The amount of the surfactant used is not particularly limited and may not be used, but is preferably 30 parts by mass or less (when two or more types of surfactants are used in combination, the total amount) per 100 parts by mass of the fibrous carbon (carbon nanofibers in the process of being ground) to be ground and dispersed, more preferably 0.1 parts by mass or more and 20 parts by mass or less, and particularly preferably 0.5 parts by mass or more and 10 parts by mass or less. If too much surfactant is used, the carbon fibers may aggregate as they dissolve vertically. As a result, the carbon nanofibers will be in an aggregated state in the dispersion, and when the dispersion is applied to an object, the physical properties of the object may be affected.
[0116] When the wet treatment is carried out, a new surfactant may be added in wet pulverization, or the surfactant that was mixed in the wet treatment may be used as it is. When a surfactant is added during wet grinding, the surfactant may be the same as or different from the surfactant used in the wet treatment.
[0117] <<<Wet grinding method, equipment and conditions>>> Only by performing wet milling can CNFs with the specific shapes (diameter, length, aspect ratio) and particle size distribution described above be produced. The wet-milling conditions are adjusted so as to obtain CNFs having the specific shapes (diameter, length, aspect ratio) described above according to the present invention.
[0118] Preferred materials for the grinding media used in wet grinding include glass, alumina, zircon (zirconia-silica ceramics), zirconia, metal (steel), and the like.
[0119] Taking a bead mill as an example, the diameter of the beads used is preferably 0.1 mm or more and 3 mm or less, more preferably 0.2 mm or more and 2 mm or less, and particularly preferably 0.3 mm or more and 1 mm or less. If the bead diameter is too large, the number of beads in the bead mill container will decrease, which will reduce the number of contact points, making it impossible to crush and disperse properly, or the diameter will not be small enough to crush the beads, etc. On the other hand, if the bead diameter is too small, it may not be possible to crush and disperse properly, or crushing may take too long, etc.
[0120] The bead filling rate used in the bead mill is preferably from 45% to 90%, more preferably from 55% to 87%, and particularly preferably from 65% to 85%. If the bead filling rate is too low, the fibrous carbon is less likely to crack vertically, and it may be difficult to produce carbon nanofibers with a large aspect ratio, etc. On the other hand, if the bead filling rate is too high, it may be difficult for the stirring blades of the bead mill to rotate, etc.
[0121] The amount of fibrous carbon after dry pulverization is preferably from 1 to 20% by mass, more preferably from 3 to 15% by mass, and particularly preferably from 5 to 10% by mass, based on the entire slurry to be treated by the bead mill.
[0122] The shape of the stirring blade used in the bead mill treatment is not particularly limited. The rotation speed of the stirring blade (agitator) depends on the span length of the stirring blade and the capacity of the bead mill, but in terms of a 2 L capacity, it is preferably 600 rpm or more and 4500 rpm or less, more preferably 800 rpm or more and 4000 rpm or less, and particularly preferably 1000 rpm or more and 3500 rpm or less. The peripheral speed of the tip of the stirring blade (agitator) depends on the span length of the stirring blade, but is preferably within the range that can be calculated from the above rotation speed assuming a diameter of 20 cm. Specifically, it is preferably 5 m / s to 40 m / s, more preferably 7 m / s to 30 m / s, and particularly preferably 9 m / s to 20 m / s.
[0123] The operation method of the bead mill for grinding and dispersing may be either a circulation type or a batch type, but the circulation type is preferred. In the case of the circulation type, the material is not transferred to a container as in the batch type, so that aggregation does not progress. When using a circulation system, the degree of pulverization varies depending on the number of passes. For example, when the residence time per pass is increased, the particle size distribution becomes sharper because there is no short pass of the processed material, but the aspect ratio of the carbon nanofibers also becomes smaller. Therefore, for example, when converted to 4L, the bead mill treatment is preferably performed by circulating for 70 minutes or more and 270 minutes or less, more preferably 80 minutes or more and 230 minutes or less, and particularly preferably 90 minutes or more and 180 minutes or less.
[0124] The temperature in the wet treatment is preferably from 0° C. to 50° C., particularly preferably from 5° C. to 35° C. The bead mill may be of either a vertical or horizontal type. In addition, a commercially available bead mill can be used, such as the Dyno Mill by Willy & Bachofen (WAB) and the Bead Mill by Netsch (USA).
[0125] The time per pass (continuous operation time), the number of passes, and the total time may depend on the equipment structure, slurry concentration, grinding and dispersion conditions, the type of surfactant, etc., so it is preferable to take out the material after each pass or during the wet grinding and observe it one by one with a particle size distribution measuring device, an optical microscope, a scanning electron microscope (SEM), etc., and adjust it appropriately.
[0126] By using the above-mentioned "production method essentially involving dry pulverization and wet pulverization" and appropriately adjusting the pulverization conditions within the above-mentioned ranges, it is possible to obtain carbon nanofibers (group) having a diameter of 30 nm to 1000 nm and a length of 0.2 μm to 70 μm. It is possible to obtain a group of carbon nanofibers in which the carbon nanofibers are in a state in which they can be isolated one by one, or in which they are in a dispersed or dispersible state one by one. It is also possible to obtain carbon nanofibers (group) having a number average aspect ratio of 5 to 200. The present invention also relates to a group of carbon nanofibers produced by the method for producing a group of carbon nanofibers described above.
[0127] <<Anti-aggregation treatment>> After the wet grinding, it is particularly preferable to carry out an anti-aggregation treatment, although this is not limited thereto. Examples of the anti-agglomeration agent used in the anti-agglomeration treatment include, but are not limited to, metal-containing anti-agglomeration agents such as (composite) metal chelate compounds, (composite) metal oxide fine particles, metal-containing wax, (composite) metal ion water, etc.; coblock polymers having units such as polyester, polyacrylate, polyurethane, etc.; comb-type coblock polymers having such polymers as units; surfactants, etc. The anti-agglomeration treatment is preferably carried out by blending the anti-agglomeration agent. The aggregation prevention treatment may be carried out immediately after the above-mentioned wet pulverization, or after the water removal treatment described below, or may be carried out at both stages.
[0128] In the case where a metal-containing anti-aggregation agent as described above is used as the anti-aggregation agent in the anti-aggregation treatment, a (composite) metal chelate compound is more preferable, and metal salts such as HEDTA, EDTA, PDTA, NTA, ethylenediamine, bipyridine, phenanthroline, and porphyrin are even more preferable. Among these, metal salts (of acetic acid derivatives) such as HEDTA (hydroxyethyl ethylene diamine triacetic acid), EDTA (ethylenediaminetetraacetic acid), PDTA (1,3-propanediamine tetraacetic acid), and NTA (nitrilo triacetic acid) are particularly preferred.
[0129] As the surfactant used in the anti-aggregation treatment, an anionic surfactant, a cationic surfactant, or an amphoteric surfactant is preferably mentioned, and an anionic surfactant or an amphoteric surfactant is more preferably mentioned. Although not limited thereto, particularly preferred specific surfactants include those similar to those described in the above sections of <Wet treatment> and <Wet grinding>.
[0130] The type of anti-aggregation agent, such as a metal-containing anti-aggregation agent, a surfactant used in the anti-aggregation treatment, or a coblock polymer, is determined taking into consideration the surface condition of the object to be prevented from agglomeration immediately before the anti-aggregation treatment. When the types of anti-aggregation agents such as metal-containing anti-aggregation agents, surfactants, and coblock polymers are as described above, aggregation is less likely to occur during the removal treatment step of the dispersion medium (water) and over time thereafter, and storage stability is improved.
[0131] The amount of "anti-agglomerating agents, such as metal-containing anti-agglomerating agents, such as (composite) metal chelate compounds; surfactants used in anti-agglomerating treatment; coblock polymers; and the like" used is not particularly limited, but is preferably added in an amount of 0.1 mass% or less, more preferably 0.0001 mass% or more and 0.06 mass% or less, and particularly preferably 0.0002 mass% or more and 0.03 mass% or less, based on the total amount of the slurry after wet grinding (the total amount when two or more types of anti-agglomerating agents are used in combination).
[0132] The amount of the anti-agglomeration agent used is not particularly limited, but is preferably added in an amount of 1 mass % or less, more preferably 0.001 mass % to 0.5 mass % or less, even more preferably 0.002 mass % to 0.3 mass % or less, and particularly preferably 0.003 mass % to 0.1 mass % or less, relative to the total amount of the object to be prevented from agglomeration, such as carbon nanofibers (the total amount when two or more types of anti-agglomeration agents are used in combination).
[0133] When the blending amount of the anti-aggregation agent, i.e., "metal-containing anti-aggregation agent, surfactant used in the anti-aggregation treatment, coblock polymer, etc." is within the above-mentioned range, aggregation is less likely to occur during the removal treatment step of the dispersion medium (water) and over time thereafter, and storage stability is improved.
[0134] The stirring during the aggregation prevention treatment is not particularly limited, but examples thereof include stirring with a hand mixer, etc. The stirring speed is not particularly limited, but is preferably 300 to 1200 rpm, and particularly preferably 500 to 1000 rpm. The temperature for the aggregation prevention treatment is not particularly limited, but is preferably from 20°C to 100°C, more preferably from 40°C to 90°C, and particularly preferably from 60°C to 80°C.
[0135] <<Water removal treatment>> The water removal treatment is not particularly limited and can be performed by reducing pressure and / or increasing temperature. It is particularly preferable to semi-dry up the material by cyclone separation and recovery, and then remove water (dry) by reducing pressure and / or increasing temperature in an oven. The temperature for the water removal treatment is not particularly limited, but is preferably from 40°C to 160°C, more preferably from 55°C to 150°C, and particularly preferably from 70°C to 130°C. The water removal process results in solid (powdered) CNF.
[0136] <Solid (powdered) carbon nanofibers> Furthermore, in order to remove surfactants and the like, it is also preferable to heat the mixture at, for example, 250° C. or higher and 400° C. or lower. Since the CNF in the present invention has good dispersibility by itself, it is also preferable that no dispersant or surfactant is attached to its surface.
[0137] It is also preferable to carry out the above-mentioned anti-agglomeration treatment after the above-mentioned water removal treatment. That is, it is also preferable to mix the above-mentioned anti-agglomeration agent and surfactant into the concentrated slurry or powder after the above-mentioned water removal treatment.
[0138] The powdered CNF produced by the method of the present invention (even if solidified) is easily dispersed in resin emulsions and resins themselves, and diffuses without agglomeration. The resins include thermoplastic resins and thermosetting resins, and for thermosetting resins, it disperses well in the base resin, the curing agent, and the mixture before curing.
[0139] The resin emulsion is not limited, but examples thereof include (meth)acrylic resins, styrene-maleic anhydride resins, and urethane resins, which have particularly good dispersibility. As the thermoplastic resins and thermosetting resins, those described below are preferred.
[0140] <Carbon nanofiber dispersion> The thermally conductive structure of the present invention can be prepared from powdered (solid) CNF or from a CNF dispersion. The CNF dispersion has good dispersibility and can be made highly concentrated if necessary. The CNF dispersion may be the slurry itself after the above-mentioned wet grinding or after the above-mentioned anti-agglomeration treatment, or may be obtained by adding a new dispersion medium to the slurry or by replacing the dispersion medium with a new dispersion medium, or may be obtained by re-dispersing carbon nanofiber powder after the above-mentioned water removal treatment.
[0141] [Isotropic thermally conductive filler] The thermally conductive structure of the present invention is characterized in that the base material contains the above-mentioned CNF and an isotropic thermally conductive filler.
[0142] The isotropic thermally conductive filler refers to a filler that has approximately isotropic thermal conductivity, and since it has approximately isotropic thermal conductivity, it is preferable that the particle shape is three-dimensionally isotropic, although there are no particular limitations on this.
[0143] The particle size of the isotropic thermally conductive filler is not particularly limited, but the median size D50 is preferably 0.1 μm or more and 100 μm or less, more preferably 0.2 μm or more and 70 μm or less, even more preferably 0.5 μm or more and 50 μm or less, and particularly preferably 1.0 μm or more and 30 μm or less. When a plurality of types of isotropically thermally conductive fillers are used, it is desirable that the D50 of each of them and / or the D50 as a whole be within the above range.
[0144] The isotropic thermally conductive filler preferably has a thermal conductivity at 300 K of 5 [W / (m·K)] or more and 600 [W / (m·K)] or less. A value of 12 [W / (m·K)] or more and 500 [W / (m·K)] or less is more preferable, a value of 14 [W / (m·K)] or more and 400 [W / (m·K)] or less is even more preferable, and a value of 16 [W / (m·K)] or more and 300 [W / (m·K)] or less is particularly preferable.
[0145] Within the above range, when contained in the base material together with the CNF of the present invention, good thermal conductivity is exhibited in both the non-oriented and oriented directions.
[0146] The isotropic thermally conductive filler may be either inorganic or organic, but inorganic substances (inorganic fillers) are more preferred because they have high thermal conductivity, low electrical conductivity, good fluidity, and the thermally conductive structure containing it (after curing) has high strength and high homogeneity.
[0147] The isotropic thermally conductive filler is not limited, but preferred examples include metal oxides, nitrides, metal carbides, metal hydroxides, metal carbonates, semi-metals, and the like. The isotropic thermally conductive filler may be used alone or in combination of two or more kinds. A semimetal is a material that exhibits properties intermediate between those of metals and nonmetals, and in particular, a material that has electrical conductivity intermediate between those of metals and nonmetals.
[0148] Specific preferred examples of the material include magnesium oxide (MgO); magnesium carbonate (MgCO3); magnesium hydroxide (Mg(OH)2); silicon dioxide such as fused silica and crystalline silica; aluminum oxide (alumina) (Al2O3); boron nitride such as hexagonal boron nitride (BN); silicon nitride (Si3N4); aluminum nitride (AlN); silicon carbide (SiC); and metal silicon (Si) such as polycrystalline silicon and single crystal silicon. The above specific examples include those containing impurities, anhydrides and those containing water of crystallization, and those with high or low crystallinity (presence or absence) and mixed crystals.
[0149] The isotropic thermally conductive filler is preferably subjected to a silane treatment with a silane coupling agent or other surface treatment before being contained and dispersed in a base material such as a base resin.
[0150] [Base material] The thermally conductive structure of the present invention is characterized in that the base material contains the above-mentioned CNF and the above-mentioned isotropic thermally conductive filler. That is, the thermally conductive structure of the present invention contains the following base material, the CNF, and the isotropic thermally conductive filler as essential components.
[0151] The base material in the present invention is not particularly limited, and examples thereof include organic materials such as resins, and inorganic materials such as glass and ceramics. A particularly preferred base material for the thermally conductive structure is a base resin, and examples of the base resin include thermoplastic resins and thermosetting resins.
[0152] The thermoplastic resin is preferably at least one thermoplastic resin selected from the group consisting of polyethylene, polypropylene, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl acetate, thermoplastic polyurethane, polytetrafluoroethylene, acrylonitrile butadiene styrene resin, acrylonitrile styrene resin, (meth)acrylic resin, modified silicone resin, polyamide, polyacetal, polycarbonate, (modified) polyphenylene ether, polyester, cyclic polyolefin, polyphenylene sulfide, polysulfone, polyether sulfone, polyarylate, polyether ether ketone, thermoplastic polyimide, and polyamide imide.
[0153] The CNFs of the present invention are suitably dispersed in the thermoplastic resin and, as described above, exhibit superior thermal, electrical and mechanical effects compared to other fibrous carbon and other carbon nanofiber(s).
[0154] The thermosetting resin is preferably one or more thermosetting resins selected from the group consisting of phenolic resins, epoxy resins, melamine resins, urea resins, unsaturated polyester resins, alkyd resins, silicone resins, thermosetting modified silicone resins, thermosetting polyurethanes, and thermosetting polyimides.
[0155] The CNFs of the present invention are suitably dispersed in the base resin (containing unreacted resin having functional groups, etc.) of a thermosetting resin, and / or in the curing agent (which crosslinks, reacts, and polymerizes functional groups, etc.), and / or in the "pre-curing mixture" of the base resin and the curing agent, and, as described above, exhibit superior thermal, mechanical, and electrical effects compared to other fibrous carbons and other carbon nanofibers (groups).
[0156] Particularly preferred base resins are thermoplastic or thermosetting (modified) silicone resins; epoxy resins such as flexible epoxy resins; polyurethane resins; polyalkylenes such as polyethylene and polypropylene; and the like, because they are flexible, have excellent thermal conductivity and heat resistance, have low electrical conductivity, and have physical properties other than thermal conductivity and electrical conductivity that make them suitable for the application of the thermally conductive structure.
[0157] [Base material, carbon nanofibers (CNF), isotropic thermal conductive filler content] In the thermally conductive structure of the present invention, the CNF group is preferably contained in an amount of 1.0 vol % or more and 20 vol % or less with respect to the entire thermally conductive structure. The content is more preferably from 2 vol % to 17 vol %, further preferably from 2.5 vol % to 14 vol %, and particularly preferably from 3 vol % to 8 vol %.
[0158] When the CNF group is contained within the above range, the thermally conductive structure has high thermal conductivity in both the non-oriented direction and the oriented direction, is non-conductive, and has good dispersibility, thereby achieving the effects of the present invention described above.
[0159] In the thermally conductive structure of the present invention, the isotropic thermally conductive filler is preferably contained in an amount of 20% by volume or more and 85% by volume or less based on the entire thermally conductive structure. The content is more preferably from 25 to 75% by volume, and particularly preferably from 30 to 60% by volume. When two or more types of isotropic thermally conductive fillers are contained, the above range refers to the total volume % of the two or more types.
[0160] When the isotropic thermally conductive filler is contained within the above range, the thermally conductive structure has high thermal conductivity, low electrical conductivity, and good dispersibility, and the above-mentioned effects of the present invention are achieved.
[0161] [Other components that may be contained in the thermally conductive structure] The thermally conductive structure of the present invention may contain "other components" as necessary within the range in which the effects of the present invention can be obtained. Examples of the "other components" include colorants; anti-deterioration agents; release agents such as wax; lubricants; antistatic agents; light stabilizers; adhesion promoters; other organic and inorganic fillers; processing aids for the base material; flame retardants; plasticizers; other long and thin fibrous carbons (carbonaceous materials) such as other CNTs and CMFs; and the like. These "other components" may be used alone or in combination of two or more. The content thereof is appropriately determined.
[0162] [Molded body, coating film, sheet, adhesive layer] The thermally conductive structure of the present invention is used by being attached, adhered, or placed in close proximity to a material, component, element, structure, etc., for which a rise in temperature is to be avoided. In this case, the specific form of the above-mentioned "thermally conductive structure of the present invention" is preferably a molded body, a coating film, a sheet, an adhesive layer, etc. Therefore, the present invention also relates to a molded body, a coating film, a sheet, or an adhesive layer, which is characterized by being the above-mentioned thermally conductive structure.
[0163] [Adhesives, paints, and compositions for preparing thermally conductive structures] The thermally conductive structure of the present invention is preferably used in the above-mentioned form, and in order to prepare the form, an adhesive, a paint, a composition for preparing a thermally conductive structure, etc. can be used. Using these products, a molded body, a coating film, a sheet, an adhesive layer, etc. can be obtained. Therefore, the present invention also relates to an adhesive, a coating material, or a composition for preparing a thermally conductive structure, which comprises the above-mentioned composition for a thermally conductive structure.
[0164] The CNF in the present invention can be provided as a raw material for preparing "thermally conductive structures in the form of, for example, molded bodies, coating films, sheets, adhesive layers, etc."
[0165] <Action / Principle> Although the present invention is not limited to the scope in which the following action and principle are established, in the present invention, it is believed that the physical properties such as thermal conductivity, non-conductivity, dispersibility, etc., as described above are improved due to the shape and size (distribution), aspect ratio, and (chemical or physical) surface state of the CNF. It is believed that the suitable size and aspect ratio (and surface state) of the CNF improves the thermal properties as well as the dispersibility, and a thermally conductive structure with a novel composition and physical properties has been obtained. EXAMPLES
[0166] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples as long as it does not depart from the gist of the present invention.
[0167] Furthermore, unless otherwise specified, in tables and figures, "volume %" and "%" refer to the volume % of the content relative to the total volume of the structure (hereinafter, sometimes referred to as the "test specimen") used to measure thermal conductivity, etc. (calculated from the mass, taking into account the specific gravity). The median diameter is also abbreviated as "D50".
[0168] Manufacturing Example 1 [Preparation of carbon nanofiber(s)] <Dry grinding> "Chopped fibers of approximately 6 mm," which are random mesophase pitch-based fibrous carbon that has not been subjected to sizing treatment, were dry-ground at 30°C for 10 minutes using a "shear and impact grinder with blades" as shown in Figure 9, without pre-grinding, so that 90% of the total particles were in the diameter 10 μm and length range of 10 μm to 40 μm. 1000 g of the fibers were dry-ground for 10 minutes at 30°C.
[0169] <Wet processing> A slurry was obtained by mixing and stirring 100 parts by mass of dry-milled fibrous carbon (e.g., Figure 5(a)(b)) that had not been subjected to heat treatment, 1 part by mass of a wetting agent (surfactant), and 1,500 parts by mass of purified water. Here, the wetting agent (surfactant) was an ammonium salt of a compound having an acid group.
[0170] The above slurry was subjected to a wetting treatment by stirring at 800 rpm with a hand mixer at 30° C. for 10 minutes.
[0171] <Wet grinding> Using a bead mill with a volume of 0.6 L, beads with a diameter of 0.3 mm, a bead filling rate of 60%, a vessel motor rotation speed of 1500 rpm, and a tubular circulation pump with a transfer rate of 500 mL per minute, 4 L of the slurry obtained above was circulated for 90 minutes or more.
[0172] <Anti-aggregation treatment> Only 3500 mL of the obtained slurry was transferred from the container of the bead mill to a separate container, and then 0.01% by mass of a coblock polymer was added as an anti-aggregation agent with respect to the entire slurry (3500 mL). After the addition, the mixture was stirred at room temperature (15 to 25° C.) at 800 rpm for 5 minutes using a hand mixer to carry out an anti-aggregation treatment.
[0173] <Water removal treatment> After applying heat and reducing pressure, the semi-dried material was collected using a cyclone separation and collection method, and heated in an oven at 150°C for 240 minutes to remove the water and prepare solid carbon nanofibers. After that, it was heated in an oven at 260°C for 1 hour to remove surfactants, etc.
[0174] Evaluation example 1 [Characteristics of the carbon nanofibers obtained in Production Example 1] <Dispersibility> The powdered carbon nanofibers obtained by the above method (Manufacturing Example 1) and the carbon nanofibers in the dispersion (slurry) before the water removal treatment were observed with an optical microscope and a scanning electron microscope and measured as described above. All of the obtained carbon nanofibers had a diameter of 30 nm or more and 1000 nm or less and a length of 0.2 μm or more and 70 μm or less, with 90% of the total number of carbon nanofibers distributed within the above range.
[0175] In fact, the number average diameter of the carbon nanofiber group was 700 nm for both the powdered carbon nanofibers and the carbon nanofibers in the slurry, and the number average length was 14 μm for both.
[0176] It was confirmed as follows that the obtained carbon nanofiber group (CNF) was well dispersed in the base material, that is, dispersed in the base material such as various base resins or in a part thereof.
[0177] The obtained solid (powdered) carbon nanofibers were added to an aqueous emulsion of acrylic resin, an aqueous emulsion of styrene-maleic anhydride resin, an aqueous emulsion of polyurethane resin, or a silicone resin, and stirred normally, so that the carbon nanofibers were dispersed approximately one by one from the solid carbon nanofibers in the water or resin. They did not aggregate during dispersion, and did not aggregate over time.
[0178] In addition, when the obtained solid carbon nanofibers were dispersed in a base resin made of any general-purpose thermoplastic resin using a conventional kneader, the fibers were dispersed well and approximately one by one in the base resin.
[0179] In addition, when the obtained solid carbon nanofiber groups were dispersed into the curing agent side of any general-purpose thermosetting resin and into the resin before thermosetting (uncured resin) of any general-purpose thermosetting resin using a conventional stirrer, the carbon nanofibers were dispersed favorably approximately one by one into the curing agent or uncured resin.
[0180] In addition, when the curing agent in which the carbon nanofibers were dispersed was mixed with "uncured base resins containing epoxy resin, urethane resin, and silicone resin," all of the resins remained dispersed and did not aggregate, making them suitable for use as thermosetting resins.
[0181] Furthermore, when the obtained solid carbon nanofibers were blended into an "uncured mixed liquid (uncured resin) made by mixing the main agent of a thermosetting resin and a curing agent," the fibers were dispersed appropriately in the uncured resin, approximately one by one. As described later, the obtained solid carbon nanofibers were dispersed in uncured silicone gel using a conventional stirrer, and the fibers were dispersed appropriately in the uncured resin approximately one by one.
[0182] It was found that the solid (powdered) carbon nanofibers obtained in Production Example 1 had extremely excellent dispersibility.
[0183] <Comparison with carbon nanofibers prepared using other raw materials> Carbon nanofiber groups were prepared (or were attempted to be prepared) in the same manner as in Production Example 1, except that isotropic pitch-based fibrous carbon, radial mesophase pitch-based fibrous carbon, and onion mesophase pitch-based fibrous carbon were used as raw materials instead of random mesophase pitch-based fibrous carbon.
[0184] The ease of production of "carbon nanofibers having a diameter of 30 nm or more and 1000 nm or less, a length of 0.2 μm or more and 70 μm or less, and preferably a number average aspect ratio of 3 or more" was as follows. In addition, the further up (to the left) you go with ">>", ">", and ">≒, the more superior it is. The degree of superiority or inferiority is also indicated with ">>", ">", and ">≒. Random mesophase pitch-based fibrous carbon >>Radial type mesophase pitch fibrous carbon ≒ Onion-type mesophase pitch-based fibrous carbon >>Isotropic pitch-based fibrous carbon (not actually prepared) ≒ PAN-based fibrous carbon (Comparative Production Example 1 (below), which could not actually be prepared)
[0185] The order of superiority was also roughly the same for dispersibility, dispersion stability, high-concentration dispersibility, thermal properties, mechanical properties, and electrical properties. The order of superiority also seemed to be the same as above, with the order being ">>", ">", and ≒.
[0186] Comparative Manufacturing Example 1 An attempt was made to prepare a carbon nanofiber group in the same manner as in Production Example 1, except that PAN-based fibrous carbon was used as the raw material instead of the pitch-based fibrous carbon of Production Example 1. However, no carbon nanofiber group was obtained in which the number average aspect ratio was less than 3, the diameter was 30 nm or more and 1000 nm or less, and the length was 0.2 μm or more and 70 μm or less, with 50% or more of the total carbon nanofibers distributed within the above ranges.
[0187] Manufacturing Example 2 Carbon nanofiber groups were obtained in the same manner as in Production Example 1, except that milled fibers having a diameter of 10 μm and a length of 70 μm were used as the raw material instead of the chopped fibers. Since there were many short fibers with lengths of approximately 1 μm, the number average aspect ratio tended to be small, but a good group of carbon nanofibers was obtained and the dispersibility and other aspects were also evaluated as good.
[0188] Production Example 3 A long fiber bobbin type was used as the raw material instead of the "6 mm chopped fiber" in Production Example 1. Although pre-pulverization with a cutter mill was necessary, carbon nanofiber groups were obtained well in the same manner as in Production Example 1, and the evaluation of dispersibility, etc. was also good.
[0189] Production Example 4 The same treatment as in Production Example 1 was carried out except that in the dry grinding step of Production Example 1, a full airflow type grinder that does not use impellers, blades, etc. (or does not use impellers, etc.), such as a jet mill, cyclone mill, tornado mill, or dream mill, was used instead of the "mill using shear and impact with blades."
[0190] Carbon nanofibers were obtained satisfactorily, and the evaluation of dispersibility and the like was also favorable. However, there was a tendency for the number average aspect ratio to become slightly smaller during the dry grinding stage, and this tendency for the number average aspect ratio to become smaller remained even after the subsequent wet grinding.
[0191] Production Example 5 Carbon nanofiber groups were obtained in the same manner as in Production Example 1, except that in place of the random mesophase pitch fibrous carbon that had not been sized in Production Example 1, a random mesophase pitch fibrous carbon that had been sized was used as the raw material, and further, a heat treatment was performed after dry grinding. The heat treatment was performed in an electric furnace at a temperature of 400° C. for 10 minutes.
[0192] The amount of epoxy resin contained in the raw materials was reduced to 0.01% by mass or less. As a result, the surfactant (wetting agent) was effectively absorbed into the filaments (in the gaps between the filaments), resulting in the creation of carbon nanofibers with a large number-average aspect ratio.
[0193] Production Example 6 In Production Example 1, the wetting treatment was not carried out. Instead, the same wetting agent (surfactant) as that used in the wetting treatment in Production Example 1 was blended as a surfactant in the wet grinding. Other than that, the same procedure as in Production Example 1 was carried out to obtain carbon nanofiber groups.
[0194] Although the effect of the wetting agent (surfactant) was slightly less than in Production Example 1 and the number average aspect ratio tended to be smaller, good carbon nanofiber groups were obtained and the dispersibility and other properties were also evaluated as good.
[0195] Production Example 7 A plurality of types of carbon nanofiber groups were obtained in the same manner as in Production Example 6, except that a carbobetaine type, imidazoline type, amidobetaine type, amidosulfobetaine type, or amidoamine oxide type amphoteric surfactant was used instead of the surfactant used in Production Example 6 (the wetting agent (surfactant) used in the wetting treatment in Production Example 1). Those using amphoteric surfactants showed good high foaming properties in hard water and over a wide pH range. As the carbobetaine type amphoteric surfactant, Softazoline (manufactured by Kawaken Fine Chemicals Co., Ltd.) was used.
[0196] As in Production Examples 1 and 6, carbon nanofibers were obtained satisfactorily, and the evaluation of dispersibility and the like was also favorable.
[0197] Production Example 8 Carbon nanofiber groups were obtained in the same manner as in Production Examples 1 and 5, except that the raw material in Production Example 5 was used and the aggregation prevention treatment in Production Example 1 was not carried out.
[0198] In either case, carbon nanofibers were obtained satisfactorily, and the evaluation of dispersibility, etc. was also good. However, the obtained carbon nanofiber dispersion tended to aggregate slightly over time compared to the dispersion obtained in Production Example 1, but this was not at a level that caused any problems.
[0199] Production Example 9 A carbon nanofiber dispersion was obtained without performing the water removal treatment in Production Example 1. The dispersion had excellent dispersibility and could be used for the next application as it was.
[0200] Manufacturing Example 10 In the aggregation prevention treatment of Production Example 1, highly condensed sodium naphthalenesulfonate, which is an anionic surfactant, was added in an amount of 5 mass% to the entire slurry (3500 mL) instead of the composite metal chelate used in Production Example 1. That is, 50 mass parts were added to 100 mass parts of the target. Carbon nanofiber groups were obtained in the same manner as Production Example 1 except for the above.
[0201] Carbon nanofibers were obtained satisfactorily, and the evaluations of dispersibility and dispersion stability were also good.
[0202] Manufacturing Example 11 In Production Examples 1 and 10, the order of the anti-agglomeration treatment and the water removal treatment was reversed, and the target material that had been subjected to the water removal treatment to turn into a thick slurry or powder was mixed with the "surfactant that is an anionic surfactant" in Production Example 10 or the "composite metal chelate that is an anti-agglomeration agent" in Production Example 1. Carbon nanofiber groups were obtained in the same manner as in Production Examples 1 and 10, except that the order of the anti-agglomeration treatment and the water removal treatment was reversed, and the target material that had been subjected to the water removal treatment to turn into a thick slurry or powder was mixed with the "surfactant that is an anionic surfactant" in Production Example 10 or the "composite metal chelate that is an anti-agglomeration agent" in Production Example 1.
[0203] Carbon nanofibers were obtained satisfactorily, and the evaluations of dispersibility and dispersion stability were also good.
[0204] Comparative Manufacturing Example 2 In Production Example 1, an attempt was made to obtain carbon nanofibers by dry grinding alone, without wet grinding, but a group of carbon nanofibers in which 50% or more of the total carbon nanofibers were distributed within the above ranges in diameter to 30 nm and 1000 nm in length were not obtained.
[0205] Manufacturing Example 12 In Production Example 1, carbon nanofibers were obtained by wet pulverization alone, without performing dry pulverization. However, the pulverization did not proceed smoothly, and it was difficult to obtain a group of carbon nanofibers in which 50% or more of the total carbon nanofibers were distributed within the above ranges, with the diameter being 30 nm or more and 1000 nm or less and the length being 0.2 μm or more and 70 μm or less.
[0206] Example 1 [(spherical alumina 55% by volume + CNF 5% by volume) / silicone resin] <Resin mixing> Using a vacuum rotary stirrer, 50 parts by mass of liquid A and 50 parts by mass of liquid B of a two-component curing silicone gel (KE-1051J-A / B, manufactured by Shin-Etsu Chemical Co., Ltd.) were stirred and kneaded at 720 rpm for 2 minutes to obtain a kneaded liquid.
[0207] <Combination of carbon nanofibers (CNF)> To 7.1 g (equivalent to 40 volume %) of the "kneaded liquid of silicone gel A liquid and B liquid" obtained above, 2.1 g (equivalent to 5 volume %) of the CNF obtained in Production Example 1 was added, and while reducing the pressure to -98 kPa, the mixture was stirred at 45 rpm for 1 minute, and then, while maintaining the reduced pressure at -98 kPa, the mixture was stirred and kneaded for 3 minutes at 720 rpm to obtain a "CNF kneaded product". The dispersibility of the CNF was good.
[0208] <Silane treatment of isotropic thermally conductive filler> A mixture of 1 part by mass of decyltrimethoxysilane and 9 parts by mass of ethanol was mixed with 100 parts by mass of spherical alumina manufactured by Denka Co., Ltd. (DAM-10, D50=11.3 μm) and Denka Co., Ltd. (ASFP-05S, D50=0.6 μm) (see Table 1 for the mixing ratio of the two types of spherical alumina) while stirring the spherical alumina powder, left in a sealed state for 24 hours or more, and then dried at 105°C for 24 hours or more to perform a silane treatment on the spherical alumina powder.
[0209] <Mixing of isotropic thermally conductive filler> The above-mentioned silane-treated spherical alumina was added to the above-mentioned CNF kneaded product and kneaded to obtain a silicone resin kneaded product containing "55.0 volume % of spherical alumina and 5.0 volume % of CNF" in total of 50 g.
[0210] Specifically, 29.7 g (equivalent to 40 volume %) of silane-treated spherical alumina (DAM-10) manufactured by Denka Co., Ltd. and 11.1 g (equivalent to 15 volume %) of silane-treated spherical alumina (ASFP-05S) manufactured by Denka Co., Ltd. were added to the above "CNF kneaded product", and the mixture was stirred at 45 rpm for 1 minute while reducing the pressure to -98 kPa. Thereafter, the mixture was stirred and kneaded for 3 minutes at 720 rpm while maintaining the reduced pressure of -98 kPa to obtain a kneaded product.
[0211] <Molding / hardening> The kneaded material obtained above was removed from the stirring vessel, and the mixture was filled into a 30 mL polypropylene cup as a mold, and molded by tamping, etc., in three batches to prevent air bubbles from being trapped. After that, it was cured in a temperature bath at 85°C for 16 hours or more to obtain a cured structure.
[0212] <Preparation of test specimen> The above hardened structure was marked so that the molding direction could be identified when it was removed from the mold, and a 2 mm thick sheet was cut out of the hardened structure with a cutter knife or the like parallel to the direction of pressure (tamping) during molding and hardening to prepare a test specimen for measuring thermal conductivity in the orientation direction. Similarly, a specimen was cut from the sheet perpendicular to the direction of pressure during molding and curing to prepare a test specimen for measuring thermal conductivity in the non-oriented direction.
[0213] Example 2 [(spherical alumina 57% by volume + CNF 3% by volume) / silicone resin] In Example 1, the CNF was blended, the silane-treated spherical alumina was kneaded, molded and cured, and the test specimens were prepared (cut out) in the same manner as in Example 1, except that in Example 1, "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin" was replaced with "(spherical alumina 57 vol% + CNF 3 vol%) / silicone resin."
[0214] Specifically, in the same manner as in Example 1, 7.0 g (corresponding to 40 volume %) of the "mixture of silicone gel A liquid and B liquid", 1.2 g (corresponding to 3 volume %) of CNF, 29.3 g (corresponding to 40 volume %) of silane-treated spherical alumina (DAM-10) manufactured by Denka Co., Ltd., and 12.5 g (corresponding to 17 volume %) of silane-treated spherical alumina (ASFP-05S) manufactured by Denka Co., Ltd. were kneaded together to obtain a kneaded product of 50 g in total containing 57.0 volume % of spherical alumina and 3.0 volume % of CNF. Next, the above kneaded product was molded and cured in the same manner as in Example 1, and a test specimen was prepared (cut out).
[0215] Example 3 [(spherical alumina 58% by volume + CNF 2% by volume) / silicone resin] In Example 1, the CNF was blended, the silane-treated spherical alumina was kneaded, molded and cured, and the test specimens were prepared (cut out) in the same manner as in Example 1, except that in Example 1, "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin" was replaced with "(spherical alumina 58 vol% + CNF 2 vol%) / silicone resin."
[0216] Specifically, in the same manner as in Example 1, 7.0 g (corresponding to 40 volume %) of the "mixture of silicone gel A liquid and B liquid", 0.8 g (corresponding to 2 volume %) of CNF, 29.1 g (corresponding to 40 volume %) of silane-treated spherical alumina (DAM-10) manufactured by Denka Co., Ltd., and 13.1 g (corresponding to 18 volume %) of silane-treated spherical alumina (ASFP-05S) manufactured by Denka Co., Ltd. were kneaded together to obtain a kneaded product of 50 g in total containing 58.0 volume % of spherical alumina and 2.0 volume % of CNF. Next, the above kneaded product was molded and cured in the same manner as in Example 1, and test specimens were prepared (cut out).
[0217] Example 4 [(spherical alumina 55% by volume + CNF 2.5% by volume + carbon milled fiber 2.5% by volume) / silicone resin] In Example 1, the "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin" was replaced with "(spherical alumina 55 vol% + CNF 2.5 vol% + carbon milled fiber (CMF) 2.5 vol%) / silicone resin." Except for this, the same procedures as in Example 1 were carried out for blending CNF and CMF, kneading the silane-treated spherical alumina, molding and curing, and preparation (cutting) of test specimens.
[0218] Specifically, in a manner similar to that of Example 1, 7.1 g (equivalent to 40 volume %) of "mixture of silicone gel A liquid and B liquid", 1.1 g (equivalent to 2.5 volume %) of CNF, 1.1 g (equivalent to 2.5 volume %) of "K223HM-Milled" (fiber length 50 μm) manufactured by Mitsubishi Chemical Corporation, 29.6 g (equivalent to 40 volume %) of silane-treated spherical alumina (DAM-10) manufactured by Denka Co., Ltd., and 11.1 g (equivalent to 15 volume %) of silane-treated spherical alumina (SFP-05S) manufactured by Denka Co., Ltd. were kneaded to obtain a total of 50 g of a kneaded product containing 55 volume % spherical alumina, 2.5 volume % CNF, and 2.5 volume % CMF. Next, the above kneaded product was molded and cured in the same manner as in Example 1, and test specimens were prepared (cut out).
[0219] Comparative Example 1 [Spherical alumina 60% by volume / silicone resin] In Example 1, the silane-treated spherical alumina was kneaded, molded, cured, and test specimens were prepared (cut out) in the same manner as in Example 1, except that no CNF was added, i.e., "spherical alumina 60 volume % / silicone resin" was used instead of "(spherical alumina 55 volume % + CNF 5 volume %) / silicone resin."
[0220] Specifically, in the same manner as in Example 1, 28.8 g (equivalent to 40 volume %) of silane-treated spherical alumina (DAM-10) (D50=11.3 μm) manufactured by Denka Co., Ltd. and 14.4 g (equivalent to 20 volume %) of silane-treated spherical alumina (ASFP-05S) (D50=0.6 μm) manufactured by Denka Co., Ltd. were added to 6.9 g (equivalent to 40 volume %) of the "mixture of silicone gel A liquid and B liquid", and the mixture was stirred at 45 rpm for 1 minute while reducing the pressure to -98 kPa, and then stirred and kneaded at 720 rpm for 3 minutes while maintaining the reduced pressure of -98 kPa. As a result, a total of 50 g of kneaded material containing no CNF and containing 60 volume % spherical alumina was obtained.
[0221] The reason why "spherical alumina 60 volume %" is used is that in the case of spherical alumina, 55 to 60 volume % is a suitable content as an isotropic thermally conductive filler in terms of viscosity, kneadability, moldability, etc. The same applies to Examples 1 to 4.
[0222] Comparative Example 2 [Aluminum nitride 35% by volume / silicone resin] In Example 1, (1) CNF was not included, and (2) aluminum nitride was used instead of spherical alumina as the isotropic thermally conductive filler, so that [aluminum nitride 35 volume % / silicone resin] was used instead of "(spherical alumina 55 volume % + CNF 5 volume %) / silicone resin". Except for this, the aluminum nitride was kneaded, molded, cured, and test specimens were prepared (cut out) in the same manner as in Example 1. That is, the isotropic thermally conductive filler was kneaded, molded and cured, and test specimens were prepared (cut out) in the same manner as in Comparative Example 1, except that 35% by volume of aluminum nitride was used instead of 60% by volume of spherical alumina in Comparative Example 1.
[0223] Specifically, 32.6 g (corresponding to 35 volume %) of aluminum nitride (AlN1501) (D50=19.7 μm) manufactured by Resonac Corporation was added to 17.4 g (corresponding to 65 volume %) of the "kneaded liquid of silicone gel A liquid and B liquid" obtained in Example 1, and the mixture was stirred at 45 rpm for 1 minute while reducing the pressure to -98 kPa, and then stirred and kneaded at 720 rpm for 3 minutes while maintaining the reduced pressure of -98 kPa. As a result, a total of 50 g of kneaded material containing no CNF and containing 35 volume % aluminum nitride was obtained.
[0224] The reason why "aluminum nitride 35 volume %" is used is that in the case of aluminum nitride, 30 to 35 volume % is a suitable content as an isotropic thermally conductive filler in terms of viscosity, kneadability, moldability, etc. The same applies to Example 5.
[0225] Comparative Example 3 [Metallic silicon 45% by volume / silicone resin] In Example 1, the metal silicon was mixed, molded, cured, and test specimens were prepared (cut out) in the same manner as in Example 1, except that, instead of "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin", (1) CNF was not included, and (2) metal silicon was used instead of spherical alumina as the isotropic thermally conductive filler. That is, the isotropic thermally conductive filler was mixed, molded and cured, and a test specimen was prepared (cut out) in the same manner as in Comparative Example 1, except that the spherical alumina (60 volume %) was replaced by metallic silicon (45 volume %).
[0226] Specifically, 33.4 g (45 vol %) of metal silicon (D50=22.2 μm) manufactured by Kojundo Chemical Laboratory Co., Ltd. was added to 16.6 g (55 vol %) of the "mixture of silicone gel A and B liquids" obtained in Example 1, and the mixture was stirred at 45 rpm for 1 minute while reducing the pressure to -98 kPa, and then stirred and kneaded at 720 rpm for 3 minutes while maintaining the reduced pressure of -98 kPa. As a result, a total of 50 g of a kneaded material containing no CNF and containing 45 volume % metallurgical silicon was obtained.
[0227] The reason why the content is set to "45% by volume of metallic silicon" is that, in the case of metallic silicon, 40 to 45% by volume is a suitable content for an isotropic thermally conductive filler in terms of viscosity, kneadability, moldability, etc. The same applies to Example 6.
[0228] Comparative Example 4 [Silicon carbide 60% by volume / silicone resin] In Example 1, the silicon carbide was mixed, molded, cured, and test specimens were prepared (cut out) in the same manner as in Example 1, except that, instead of "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin", (1) CNF was not included, and (2) silicon carbide was used instead of spherical alumina as the isotropic thermally conductive filler. That is, the isotropic thermally conductive filler was mixed, molded and cured, and test specimens were prepared (cut out) in the same manner as in Comparative Example 1, except that 60 volume % of spherical alumina in Comparative Example 1 was replaced with 60 volume % of silicon carbide.
[0229] Specifically, 41.8 g (corresponding to 60 volume %) of silicon carbide (#400, random shape) (D50=30.01±2 μm) manufactured by Shinano Electric Smelting Co., Ltd. was added to 8.2 g (corresponding to 40 volume %) of the "mixture of silicone gel A liquid and B liquid" obtained in Example 1, and the mixture was stirred at 45 rpm for 1 minute while reducing the pressure to -98 kPa, and then stirred and kneaded at 720 rpm for 3 minutes while maintaining the reduced pressure of -98 kPa. As a result, a total of 50 g of kneaded material containing no CNF and containing 60.0 volume % silicon carbide was obtained.
[0230] The reason why "60 volume % silicon carbide" is used is that in the case of silicon carbide, 55 to 60 volume % is the optimum content as an isotropic thermally conductive filler in terms of viscosity, kneadability, moldability, etc. The same applies to Example 7.
[0231] Example 5 [(Aluminum nitride 30% by volume + CNF 5% by volume) / silicone resin] In Example 1, aluminum nitride was used as the isotropic thermally conductive filler instead of "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin" and "(aluminum nitride 35 vol% + CNF 5 vol%) / silicone resin" was used. Except for this, kneading, molding, curing, and preparation (cutting) of test specimens were performed in the same manner as in Example 1. That is, molding, curing, and preparation (cutting) of test specimens were performed in the same manner as in Comparative Example 2, except that in Comparative Example 2, the amount of aluminum nitride was reduced by 5 volume % and 5 volume % of CNF was added.
[0232] Specifically, 18.0 g (corresponding to 60 volume %) of the "kneaded liquid of silicone gel A liquid and B liquid" obtained in Example 1, 3.2 g (corresponding to 5 volume %) of CNF, and 28.8 g (corresponding to 35 volume %) of aluminum nitride (AlN1501) (D50=19.7 μm) manufactured by Resonac Co., Ltd. were kneaded to obtain a kneaded product containing 35 volume % of aluminum nitride and 5 volume % of CNF in total of 50 g.
[0233] Example 6 [(metallic silicon 40% by volume + CNF 5% by volume) / silicone resin] In Example 1, metal silicon was used as the isotropic thermally conductive filler instead of "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin" and "(metal silicon 40 vol% + CNF 5 vol%) / silicone resin" was used. Except for this, kneading, molding, curing, and preparation (cutting) of test specimens were performed in the same manner as in Example 1. That is, molding, curing, and preparation (cutting) of test specimens were performed in the same manner as in Comparative Example 3, except that in Comparative Example 3, the amount of metallic silicon was reduced by 5 volume % and 5 volume % of CNF was added.
[0234] Specifically, 16.7 g (corresponding to 55 volume %) of the “mixture of silicone gel A liquid and B liquid” obtained in Example 1, 3.5 g (corresponding to 5 volume %) of CNF, and 29.8 g (corresponding to 40 volume %) of metallic silicon were kneaded to obtain a total of 50 g of a mixture of 40% metallic silicon and 5% CNF.
[0235] Example 7 [(silicon carbide 55% by volume + CNF 5% by volume) / silicone resin] In Example 1, silicon carbide was used as the isotropic thermally conductive filler instead of "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin", and "(silicon carbide 55 vol% + CNF 5 vol%) / silicone resin" was used. Except for this, kneading, molding, curing, and preparation (cutting) of test specimens were performed in the same manner as in Example 1. That is, in Comparative Example 4, molding, curing, and preparation (cutting) of test specimens were performed in the same manner as in Comparative Example 3, except that the amount of silicon carbide was reduced by 5 volume % and 5 volume % of CNF was added.
[0236] Specifically, 8.4 g (corresponding to 40 volume %) of the "mixture of silicone gel A liquid and B liquid" obtained in Example 1, 2.4 g (corresponding to 5 volume %) of CNF, and 39.2 g (corresponding to 55 volume %) of silicon carbide (#400, random shape) were kneaded to obtain a total of 50 g of a mixture of 55 volume % silicon carbide (#400, random shape) and 5 volume % CNF.
[0237] Comparative Example 5 [(spherical alumina 55% by volume + carbon milled fiber 5% by volume) / silicone resin] In Example 4, the mixture was changed from "(spherical alumina 55 vol% + CNF 2.5 vol% + carbon milled fiber 5 vol%) / silicone resin" to "(spherical alumina 55 vol% + carbon milled fiber 5 vol%) / silicone resin." Except for this, the kneading, molding, curing, and preparation (cutting) of test specimens were carried out in the same manner as in Example 4. That is, molding, curing, and preparation (cutting) of test specimens were carried out in the same manner as in Example 1, except that carbon milled fiber was used instead of CNF in Example 1.
[0238] Specifically, 7.1 g (equivalent to 40 volume %) of the "mixture of silicone gel A liquid and B liquid" obtained in Example 1, 2.1 g (equivalent to 5 volume %) of "223HM-Milled" (fiber length 50 μm) manufactured by Mitsubishi Chemical, 29.7 g (equivalent to 40 volume %) of "silane-treated spherical alumina manufactured by Denka Co., Ltd. (DAM-10)" from Example 1, and 11.1 g (equivalent to 15 volume %) of "silane-treated spherical alumina manufactured by Denka Co., Ltd. (ASFP-05S)" were kneaded together to obtain a total of 50 g of a kneaded product containing 55 volume % spherical alumina and 5 volume % CMF.
[0239] Comparative Example 6 [(spherical alumina 55% by volume + aluminum nitride 5% by volume) / silicone resin] Molding, curing, and preparation (cutting) of test specimens were performed in the same manner as in Example 1, except that 5 volume % of aluminum nitride was used instead of 5 volume % of CNF.
[0240] Specifically, 6.9 g (equivalent to 40 volume %) of the "kneaded liquid of silicone gel A liquid and B liquid" obtained in Example 1, 3.0 g (equivalent to 5 volume %) of aluminum nitride (AlN1501) (D50 = 19.7 μm) manufactured by Resonac Co., Ltd., 29.1 g (equivalent to 40 volume %) of the silane-treated spherical alumina (DAM-10) manufactured by Denka Co., Ltd. in Example 1, and 10.9 g (equivalent to 15 volume %) of the silane-treated spherical alumina (ASFP-05S) manufactured by Denka Co., Ltd. were kneaded to obtain a kneaded product containing 55 volume % of spherical alumina and 5 volume % of aluminum nitride in total of 50 g.
[0241] Comparative Example 7 [(spherical alumina 57% by volume + aluminum nitride 3% by volume) / silicone resin] In Example 2, molding, curing, and preparation (cutting) of test specimens were performed in the same manner as in Example 1, except that 3 volume % of aluminum nitride was used instead of 3 volume % of CNF.
[0242] Specifically, 6.9 g (equivalent to 40 volume %) of the "kneaded liquid of silicone gel A liquid and B liquid" obtained in Example 1, 1.8 g (equivalent to 3 volume %) of aluminum nitride (AlN1501) (D50 = 19.7 μm) manufactured by Resonac Co., Ltd., 29.0 g (equivalent to 40 volume %) of the silane-treated spherical alumina (DAM-10) manufactured by Denka Co., Ltd. in Example 1, and 12.3 g (equivalent to 17 volume %) of the silane-treated spherical alumina (ASFP-05S) manufactured by Denka Co., Ltd. were kneaded to obtain a kneaded product containing 57 volume % of spherical alumina and 3 volume % of aluminum nitride in total of 50 g.
[0243] Evaluation example 2 <Measurement of thermal conductivity> The thermal diffusivity of the sheet-shaped specimens prepared in the Examples and Comparative Examples (specific preparation methods are described in Example 1) was measured in both the non-oriented and oriented directions using an LFA 467 (optical laser flash thermal diffusivity measurement device) manufactured by NETZSCH Japan Co., Ltd. The thermal conductivity was calculated by multiplying the obtained thermal diffusivity by the specific gravity and heat capacity of the test specimen (measurement material). The specific gravity and heat capacity used in the calculation were calculated by arithmetic calculation from the literature values of each material. The results obtained are shown in Table 1 below.
[0244] [Table 1]
[0245] <Summary of Evaluation Example 2 (Thermal Conductivity) for Examples and Comparative Examples> As can be seen from Table 1, when CNF was added, the thermal conductivity increased in both the non-oriented and oriented directions, even when the content was only 5 volume % relative to the entire thermally conductive structure (see Figure 10).
[0246] This increasing trend was the same when spherical alumina, aluminum nitride, metallic silicon, or silicon carbide was used as the isotropic thermally conductive filler (see FIG. 10). The absolute value of the thermal conductivity varied depending on the type of isotropic thermally conductive filler used. This is because the optimal content (volume %) of the isotropic thermally conductive filler differs depending on the type of isotropic thermally conductive filler, and therefore an optimal content was set for each of the four types of isotropic thermally conductive fillers used.
[0247] As can be seen from Table 1, when CNF was added to spherical alumina (replacing part of the spherical alumina), even when the content was only 5 volume % relative to the entire thermally conductive structure, the thermal conductivity increased (see Figures 10 and 11), and the thermal conductivity also increased especially in the non-oriented direction (see "Comparison between Comparative Example 1 and Example 1," "Comparison between Comparative Example 2 and Example 5," "Comparison between Comparative Example 3 and Example 6," and "Comparison between Comparative Example 4 and Example 7" in Figure 10, and see comparison between Comparative Example 1 and Examples 1 and 4 in Figure 11).
[0248] On the other hand, in the case of CMF, although it is the same fibrous carbon, unlike CNF, no increase in thermal conductivity was observed in the non-oriented direction, and furthermore, the rate of increase in the oriented direction was also reduced (see comparison between Comparative Example 1 and Comparative Example 5 in Figure 11). Furthermore, in the case of aluminum nitride, no increase in thermal conductivity was observed in either the non-oriented or oriented direction (see the comparison between Comparative Example 1 and Comparative Example 6 in FIG. 11).
[0249] As can be seen from Table 1 and Figure 12, as the CNF content increased, the thermal conductivity in the non-oriented direction and the thermal conductivity in the oriented direction increased depending on the CNF content (see Figure 12). In particular, for CNF, unexpectedly, the thermal conductivity even in the non-oriented direction increased depending on the content (see Figure 12).
[0250] As can be seen from Table 1 and FIG. 13, even if the content of aluminum nitride was increased, the thermal conductivity did not increase depending on the content of aluminum nitride (see FIG. 13).
[0251] Example 8 [(spherical alumina 50% by volume + CNF 10% by volume) / silicone resin 40% by volume] The blending of CNF, kneading of the silane-treated spherical alumina, molding and curing, and preparation (cutting) of test specimens were carried out in the same manner as in Example 1, except that in Example 1, "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin 40 vol%" was used as "(spherical alumina 50 vol% + CNF 10 vol%) / silicone resin 40 vol%."
[0252] Comparative Example 8 [CNF 26% by volume / silicone resin 74% by volume] In Example 1, the "(spherical alumina 55 vol% + CNF 5 vol%) / silicone resin 40 vol%" was replaced with "CNF 26 vol% / silicone resin 74 vol%" without containing spherical alumina, which is an isotropic thermally conductive filler. The CNF was blended, molded, cured, and test specimens were prepared (cut out) in the same manner as in Example 1.
[0253] Evaluation example 3 <Non-conductive evaluation> <<How to measure volume resistivity>> The volume resistivity of the specimens obtained in the examples and comparative examples was determined in accordance with JIS K 7194 and used as the standard for evaluating non-conductivity. The thickness of the specimens was adjusted as appropriate.
[0254] <<Criteria for determining non-conductivity>> ◎: Volume resistivity is 1.0×10 2 [Ω·cm] or more, with excellent non-conductivity ○: Volume resistivity is 1.0×10 0 ~1.0×10 2 [Ω·cm] with excellent non-conductivity △: Volume resistivity is 1.0×10 -1 ~1.0×10 0 [Ω·cm] and can be used for some purposes ×: Volume resistivity is 1.0×10 -1 [Ω·cm] or less, not non-conductive (conductive)
[0255] The results, together with the compounding ratios, are summarized in Table 2. The numerical values relating to the contents in Table 2 are in terms of volume percent. The thermal conductivity [W / (m K)] in Table 2 is the average value for the oriented and non-oriented directions.
[0256] [Table 2]
[0257] <Summary of Evaluation Example 3 (Non-conductive) for Examples and Comparative Examples> As shown in Table 2, when CNF was added at 26 volume %, the thermal conductivity increased, but the electrical conductivity also increased (the non-conductivity deteriorated). The thermally conductive structures (test specimens) of Examples 1 and 8 had extremely good thermal conductivity and were also excellent in terms of non-conductivity. [Industrial Applicability]
[0258] The CNF group of the present invention, which has a special shape, size, distribution, etc., and surface condition, is a collection of individual CNFs with excellent shapes, particularly having a large aspect ratio and being moderately fine, and further contains almost no impurities, can be well dispersed in liquid media (aqueous media, oil-based media, etc.) and solid media (base resins, etc.) (molten or above the softening point or uncured), is not easily agglomerated, and can be molded by incorporating it into resin. The obtained structure has good thermal conductivity in both the non-oriented and oriented directions and can be applied to narrow spaces, so it can be widely used in various fields where high thermal conductivity properties and non-conductivity are required. [Explanation of symbols]
[0259] 10... Filament 20 Plain filament
Claims
1. A thermally conductive structure comprising a base material containing carbon nanofibers and an isotropic thermally conductive filler, The carbon nanofiber group is obtained by wet pulverization of pitch-based fibrous carbon as a raw material, and is characterized in that "the carbon nanofiber group has a diameter of 30 nm or more and 1000 nm or less, and a length of 0.2 μm or more and 70 μm or less, with 50% or more of the total number being distributed in that range." A thermally conductive structure.
2. 2. The thermally conductive structure according to claim 1, wherein the number average aspect ratio of the carbon nanofibers contained in the carbon nanofiber group is 3 or more and 200 or less.
3. 2. The thermally conductive structure according to claim 1, wherein the carbon nanofibers contained in the carbon nanofiber group have a number average diameter of 30 nm or more and 1000 nm or less and a number average length of 0.2 μm or more and 70 μm or less.
4. The thermally conductive structure according to claim 1 , wherein the carbon nanofibers contained in the carbon nanofiber group are in a state in which they can be isolated one by one, or in a dispersed or dispersible state in which they can be dispersed one by one.
5. 2. The thermally conductive structure according to claim 1, wherein the number average thickness or number average width of the elementary filaments constituting the "filaments contained in the pitch-based fibrous carbon as a raw material" is 10 nm or more and 200 nm or less.
6. The thermally conductive structure according to claim 1, wherein the carbon nanofibers of the carbon nanofiber group are constituted by an assembly of 2 to 20 individual filaments constituting the "filaments possessed by the pitch-based fibrous carbon as the raw material."
7. 2. The thermally conductive structure according to claim 1, wherein the pitch-based fibrous carbon as a raw material is mesophase pitch-based fibrous carbon.
8. 8. The thermally conductive structure according to claim 7, wherein the mesophase pitch fibrous carbon used as the raw material is a random type mesophase pitch fibrous carbon.
9. 2. The thermally conductive structure according to claim 1, wherein the wet pulverization is bead mill pulverization or ball mill pulverization carried out in an aqueous medium in the presence of a surfactant.
10. The thermally conductive structure according to claim 1, wherein the carbon nanofiber group is obtained by dry-pulverizing pitch-based fibrous carbon until the number average length is 100 μm or less, and then wet-pulverizing the same.
11. 2. The thermally conductive structure according to claim 1, wherein the isotropically thermally conductive filler is a metal oxide, a nitride, a metal carbide, a metal hydroxide, a metal carbonate, or a semi-metal.
12. 2. The thermally conductive structure according to claim 1, wherein the isotropic thermally conductive filler has a thermal conductivity of 5 [W / (m·K)] or more at 300K.
13. 2. The thermally conductive structure according to claim 1, wherein the isotropic thermally conductive filler has a thermal conductivity of 600 [W / (m·K)] or less at 300K.
14. The base material is a base resin, and the base resin is one or more thermoplastic resins selected from the group consisting of polyethylene, polypropylene, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl acetate, thermoplastic polyurethane, polytetrafluoroethylene, acrylonitrile butadiene styrene resin, acrylonitrile styrene resin, (meth)acrylic resin, modified silicone resin, polyamide, polyacetal, polycarbonate, (modified) polyphenylene ether, polyester, cyclic polyolefin, polyphenylene sulfide, polysulfone, polyether sulfone, polyarylate, polyether ether ketone, thermoplastic polyimide, and polyamide imide, or phenol resin, epoxy resin, melamine resin, urea resin (urea resin), unsaturated polyester resin, alkyd resin, silicone resin, thermosetting modified silicone resin, thermosetting polyurethane, and thermosetting polyimide. The thermal conductive structure according to claim 1, which is one or more thermosetting resins selected from the group consisting of.
15. 2. The thermally conductive structure according to claim 1, wherein the carbon nanofiber groups are contained in an amount of 1.0 volume % or more and 20 volume % or less based on the entire thermally conductive structure.
16. 2. The thermally conductive structure according to claim 1, wherein the isotropic thermally conductive filler is contained in an amount of 20% by volume or more and 85% by volume or less based on the entire thermally conductive structure.
17. 10. The thermally conductive structure of claim 1, wherein the thermally conductive structure is electrically non-conductive.
18. A molded body, a coating film, a sheet, or an adhesive layer, which is a thermally conductive structure according to any one of claims 1 to 17.
19. An adhesive, a paint, or a composition for preparing a thermally conductive structure, comprising the composition of a thermally conductive structure according to any one of claims 1 to 17.
Citation Information
Patent Citations
Ultrafine carbon fiber and method for manufacturing the same
JP2012188790A
Thermally conductive sheet and method for manufacturing thermally conductive sheet
JP2013131563A
Pitch-based extra fine carbon fiber, electrode mixture layer for nonaqueous electrolyte secondary battery, electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2017066546A
Thermally conductive sheet and manufacturing method thereof
JP2022127596A
Thermally conductive sheet and manufacturing method thereof
JP2023042619A